Composition for forming protective film against alkaline hydrogen peroxide solution, substrate for manufacturing semiconductor device, method for forming protective film, and method for forming pattern

JP7668766B2Active Publication Date: 2025-04-25SHIN ETSU CHEMICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022079075
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-01-21
Filing Date
2022-05-12
Publication Date
2025-04-25
Estimated Expiration
2042-05-12

AI Technical Summary

Technical Problem

Conventional semiconductor manufacturing processes face challenges in achieving high integration and high speed without relying on miniaturization, as existing materials lack sufficient dry etching resistance, adhesion to substrates, and resistance to wet etching solutions like alkaline hydrogen peroxide, leading to reduced yield and process tolerance.

Method used

A protective film-forming composition containing polymers with fluorine and hydroxyl groups, which form a polyimide skeleton, providing high heat resistance, adhesion, and resistance to alkaline hydrogen peroxide, enabling advanced embedding and planarization properties, suitable for both dry and wet etching processes.

Benefits of technology

The composition allows for the formation of a protective film that maintains film integrity and adhesion during high-temperature processing, reduces substrate corrosion, and enhances the yield of semiconductor devices by improving process tolerance and compatibility with wet etching solutions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000089_0000
    Figure 00000089_0000
  • Figure 00000090_0000
    Figure 00000090_0000
  • Figure 00000090_0001
    Figure 00000090_0001
Patent Text Reader

Abstract

To provide a composition for forming a protective film with the use of a polymer containing an imide group, which is cured not only in air but also under a film-forming condition in an inert gas, can form the protective film not only excellent in heat resistance and embedding and flattening characteristics of a pattern formed on a substrate but also satisfactory in adhesion to the substrate, and can also form the protective film having excellent resistance to an alkaline hydrogen peroxide solution.SOLUTION: The composition for forming the protective film against the alkaline hydrogen peroxide solution includes: a polyimide-based polymer (A), which has a repeating unit containing at least one or more fluorine atoms and hydroxyl groups, represented by the following general formula (1A), and has a specific structure in a terminal group; and an organic solvent (B).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a protective film-forming composition that provides a protective film that is resistant to wet etching solutions used in semiconductor device manufacturing processes, a substrate for semiconductor device manufacturing using the composition, a method for forming a protective film, and a pattern formation method using a multilayer resist method. [Background technology]

[0002] Traditionally, the advances in high-density integration and high-speed semiconductor devices have been achieved by miniaturizing pattern dimensions through the shortening of the wavelength of light sources in lithography (photolithography), a commonly used technology that uses light exposure. To form such fine circuit patterns on semiconductor device substrates (substrates to be processed), dry etching is typically performed using a patterned photoresist film as an etching mask. However, because no dry etching method exists that can achieve perfect etching selectivity between the photoresist film and the substrate, substrate processing using a multilayer resist method has become common in recent years. This method involves interposing an intermediate film, which has a different etching selectivity from the photoresist film (hereinafter referred to as the resist top layer), between the resist top layer and the substrate. After forming a pattern on the resist top layer, the pattern is transferred to the intermediate film by dry etching using the resist top layer pattern as a dry etching mask, and then the pattern is transferred to the substrate by dry etching using the intermediate film as a dry etching mask.

[0003] One multilayer resist method is the three-layer resist method, which can be performed using a typical resist composition used in single-layer resist methods. In this method, an organic underlayer film (hereinafter referred to as the organic film) is formed on a substrate by coating and baking an organic underlayer material composed of an organic resin-containing composition. A silicon-containing film (hereinafter referred to as the silicon intermediate film) is then formed on top of this by coating and baking a resist intermediate film material composed of a silicon-containing resin-containing composition. A typical organic photoresist film (hereinafter referred to as the resist top layer) is then formed on top of this. After patterning the resist top layer, dry etching with a fluorine-based gas plasma allows the organic resist top layer to have a good etching selectivity relative to the silicon intermediate film, allowing the resist top layer pattern to be transferred to the silicon intermediate film. This method allows for easy pattern transfer to the silicon intermediate film, even when a resist top layer that is not thick enough to directly process the substrate or does not have sufficient dry etching resistance to process the substrate is used, as the silicon intermediate film is typically thinner than the resist top layer. Subsequently, by using the pattern-transferred silicon intermediate film as a dry etching mask to transfer the pattern to the organic underlayer film by dry etching with oxygen- or hydrogen-based gas plasma, the pattern can be transferred to an organic underlayer film that has sufficient dry etching resistance for substrate processing. This pattern-transferred organic underlayer film pattern can be transferred to the substrate by dry etching using a fluorine-based gas, chlorine-based gas, or the like.

[0004] Meanwhile, miniaturization in semiconductor device manufacturing processes is approaching essential limits due to the wavelength of the light source used for optical lithography. Therefore, in recent years, efforts have been made to increase the integration density of semiconductor devices without relying on miniaturization. As one approach, semiconductor devices with complex structures such as multi-gate structures have been considered, some of which have already been put to practical use. When forming such structures using a multilayer resist method, organic film materials can be applied to fill micropatterns such as holes, trenches, and fins formed on the substrate without gaps, or to fill steps, densely patterned areas, and pattern-free areas with a film to achieve planarization. By using such organic film materials to form a flat organic underlayer film surface on a stepped substrate, film thickness variations in the silicon intermediate film and resist overlayer film formed thereon can be suppressed, thereby suppressing the reduction in focus tolerance in optical lithography and margin reduction in subsequent processing steps of the substrate. This enables semiconductor devices to be manufactured with high yields. On the other hand, in the single-layer resist method, in order to fill in steps or patterns on a substrate to be processed, the thickness of the top-layer resist film must be thick, which can lead to pattern collapse after exposure and development, or deterioration of the pattern shape due to reflection from the substrate during exposure, narrowing the tolerance for pattern formation during exposure, making it difficult to manufacture semiconductor devices with a high yield.

[0005] Because the organic film materials mentioned above require dry etching to form high-aspect-ratio patterns, they must not only have the aforementioned filling and planarization capabilities, but also high dry-etching resistance. Furthermore, the silicon interlayer on top of the organic film must also have high dry-etching resistance. Therefore, inorganic hard masks formed by CVD or ALD techniques, which have higher dry-etching resistance than silicon interlayers formed by spin coating, are often chosen as the silicon interlayer. Because the temperatures required for forming these hard masks are typically above 300°C, the organic film must also have high heat resistance to withstand these temperatures. Furthermore, to prevent peeling from the substrate during the formation of inorganic hard masks by CVD or ALD, strong adhesion to the substrate is also required. These properties are important for organic film materials with excellent process tolerance.

[0006] Furthermore, as a method for increasing the speed of next-generation semiconductor devices, the application of precision materials such as new materials with high electron mobility, such as strained silicon and gallium arsenide, and ultra-thin polysilicon films controlled to the angstrom level, is beginning to be considered. However, when such new precision materials are used on substrates to be processed, the above-mentioned organic underlayer film materials are corroded by oxygen in the air under conditions when planarizing films are formed, such as in air at temperatures above 300°C, which may prevent the semiconductor device from achieving the performance it was designed for and result in a yield that is viable for industrial production. Therefore, to avoid the yield reduction caused by substrate corrosion by air under such high-temperature conditions, organic underlayer film materials that can be formed in an inert gas environment are desired. Furthermore, substrate processing using wet etching with chemicals may be required, and in such cases, the organic underlayer film that serves as the processing mask must also be resistant to wet etchants.

[0007] Here, we will explain in detail the background behind the demand for materials compatible with wet etching processes in relation to multilayer resist methods. To improve the performance of semiconductor devices, cutting-edge semiconductor devices use technologies such as three-dimensional transistors and through-hole interconnects. The patterning process used to form structures within such semiconductor devices also employs the multilayer resist method. In such patterning, a process of removing the silicon intermediate film without damaging the pattern may be required after pattern formation. If this removal is insufficient, i.e., if the wafer is sent to the next manufacturing process while the cleaning target remains, it will significantly reduce device manufacturing yield. As such, the level of cleanliness required in cleaning processes has increased with the miniaturization of elements. However, the main constituent element of conventional silicon intermediate films and the main constituent element of semiconductor device substrates are often silicon. Therefore, even if silicon intermediate films are selectively removed by dry etching, the similar components make it difficult to minimize damage to the semiconductor device substrate. This problem cannot be solved by wet etching using a conventional hydrofluoric acid-based stripper. Therefore, it is considered to use an alkaline hydrogen peroxide solution called SC1 (Standard Clean-1), which is commonly used in semiconductor manufacturing processes, as a wet etching solution as a stripper that does not damage the semiconductor device substrate. In this case, the organic underlayer film must be resistant to alkaline hydrogen peroxide.

[0008] Another process being considered is to use an organic underlayer film as an etching mask to wet etch a substrate made of titanium nitride or other materials using alkaline hydrogen peroxide. In this case, too, the organic underlayer film must be resistant to alkaline hydrogen peroxide.

[0009] As described above, there is a need for an organic underlayer film material for semiconductor device manufacturing that has heat resistance of 300°C or higher even in an oxygen-free inert gas atmosphere, high-level filling / planarization properties, and adhesion to the substrate, as well as high compatibility with wet etching processes (i.e., resistance to alkaline hydrogen peroxide solution), and a pattern formation method using the same.

[0010] Patent Document 1 and other documents have proposed protective films with good resistance to alkaline hydrogen peroxide solutions. However, although these materials have resistance to alkaline hydrogen peroxide solutions, they have problems in that they are insufficient in terms of planarization performance on uneven substrates and high heat resistance when a hard mask is formed on the protective film by a method such as CVD or ALD.

[0011] Further, examples of compounds having an imide structure as shown in the present invention include compounds having an imide structure described in Patent Documents 2 to 6, resins having a polyimide structure described in Patent Documents 7 to 9, and Patent Document 10, which uses a compound having a bismaleimide structure. There is no description of the resistance of these materials to alkaline hydrogen peroxide solution, and the resistance of resins having a polyimide structure to alkaline hydrogen peroxide solution is not known. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] WO2017-191767 [Patent Document 2] WO2019-146378 [Patent Document 3] Japanese Patent Publication No. 2020-177225 [Patent Document 4] Patent Publication No. 2021-091841 [Patent Document 5] Japanese Patent Publication No. 2021-130763 [Patent Document 6] Japanese Patent Publication No. 2021-152639 [Patent Document 7] Japanese Patent Application Laid-Open No. 2013-137334 [Patent Document 8] Japanese Patent Application Laid-Open No. 2010-122297 [Patent Document 9] Japanese Patent Publication No. 2020-193325 [Patent Document 10] WO2018-212116 Summary of the Invention [Problem to be solved by the invention]

[0013] The present invention has been made in view of the above circumstances, and aims to provide a protective film-forming composition using a polymer containing an imide group, which is curable not only in air but also under film-forming conditions in an inert gas, and which is capable of forming a protective film that not only has excellent heat resistance and excellent embedding and planarization properties for patterns formed on a substrate, but also has good adhesion to the substrate and excellent resistance to alkaline hydrogen peroxide water, as well as a substrate for manufacturing a semiconductor device, a method for forming a protective film, and a method for forming a pattern, which use the material. [Means for solving the problem]

[0014] In order to solve the above problems, the present invention provides: (A) A polymer having a fluorine atom and a hydroxyl group, represented by either of the following (I) and (II), or a mixture of a polymer having a fluorine atom and a polymer having a hydroxyl group, represented by the following (III): (I) A polymer having a repeating unit containing at least one fluorine atom and one hydroxyl group, represented by the following general formula (1A), and having a terminal group represented by either of the following general formulas (1B) and (1C): (II) A polymer having a repeating unit containing at least one fluorine atom, represented by the following general formula (2A), and a repeating unit containing at least one hydroxyl group, represented by the following general formula (3A), wherein the terminal group is a group represented by either of the following general formulas (1B) and (1C): (III) A mixture of a polymer having a repeating unit containing at least one fluorine atom, represented by the following general formula (2A), and a terminal group represented by either of the following general formulas (1B) and (1C), and a polymer having a repeating unit containing at least one hydroxyl group, represented by the following general formula (3A), and a terminal group represented by either of the following general formulas (1B) and (1C), and (B) Organic solvent The present invention provides a protective film-forming composition for alkaline hydrogen peroxide solution, which contains: [ka] (In the formula, W1 is a tetravalent organic group which may contain one or more types of fluorine atoms or hydroxyl groups, W2 is a divalent organic group which may contain one or more types of fluorine atoms or hydroxyl groups, and at least one of W1 and W2 contains one or more fluorine atoms and at least one of W1 and W2 contains one or more hydroxyl groups.) [ka] (In the formula, W3 is a tetravalent organic group which may contain one or more types of fluorine atoms, W4 is a divalent organic group which may contain one or more types of fluorine atoms, and at least one of W3 and W4 contains one or more fluorine atoms.) [ka] (In the formula, W5 is a tetravalent organic group which may contain one or more types of hydroxyl groups, W6 is a divalent organic group which may contain one or more types of hydroxyl groups, and at least one of W5 and W6 contains one or more hydroxyl groups.) [ka] [ka] (In the formula, R1 is any of the groups represented by the following formula (1D), and two or more types of R1 may be used in combination.) [ka]

[0015] Such a protective film-forming composition cures under film-forming conditions not only in air but also in an inert gas due to the action of the terminal crosslinking groups. Furthermore, because the main chain is composed of a polyimide skeleton, it is possible to form a protective film that combines high heat resistance, excellent adhesion to substrates, and advanced embedding / planarization properties. Furthermore, the presence of fluorine atoms and hydroxyl groups in the imide group-containing polymer allows the protective film-forming composition to form a protective film with excellent alkaline hydrogen peroxide resistance. Furthermore, by combining one or more of the organic groups W1 and W2, W3 and W4, or W5 and W6 as described above, it is possible to improve thermal fluidity, heat resistance, and adhesion.

[0016] Furthermore, it is preferable that W2 in the general formula (1A) contains at least one fluorine atom and one hydroxyl group.

[0017] It is preferable that the main chain has such a partial structure from the viewpoint of achieving both adhesiveness and excellent resistance to alkaline hydrogen peroxide solution.

[0018] Furthermore, W2 in the general formula (1A) is preferably a group represented by the following general formula (1E). [ka]

[0019] It is preferable that the main chain has such a partial structure from the viewpoints of heat resistance, flatness, adhesion, and resistance to alkaline hydrogen peroxide solution.

[0020] Furthermore, W1 in the general formula (1A) is preferably any one of the groups represented by the following general formula (1F). [ka]

[0021] It is preferable that the main chain has such a partial structure from the viewpoints of heat resistance, flatness, and resistance to alkaline hydrogen peroxide solution.

[0022] Furthermore, it is preferable that the component (A') contains a polymer (IV) having a repeating unit represented by the following general formula (4A) and a terminal group represented by the following general formula (2C). [ka] (In the formula, W7 is a tetravalent organic group, and W8 is a divalent organic group.) [ka] (In the formula, R2 represents a monovalent organic group having 1 to 10 carbon atoms, n1 represents an integer of 0 or 1, and n2 and n3 satisfy the relationship 1≦n2≦6 and 0≦n3≦6, and also satisfy the relationship 1≦n2+n3≦6.)

[0023] It is preferable to contain a polymer (IV) having a hydroxyl group at the terminal group from the viewpoint of resistance to alkaline hydrogen peroxide solution.

[0024] The weight average molecular weight of the component (A) is preferably 1,000 to 10,000.

[0025] A protective film-forming composition containing the polymer (A) having an Mw in this range can suppress outgassing during baking without impairing solubility in organic solvents.

[0026] Furthermore, the component (B) is preferably a mixture of one or more organic solvents having a boiling point of less than 180°C and one or more organic solvents having a boiling point of 180°C or higher.

[0027] In such a protective film-forming composition, the addition of a high-boiling point solvent to the polymer (A) provides the film with thermal fluidity, resulting in a protective film-forming composition that also has high filling / planarizing properties.

[0028] The protective film-forming composition preferably further contains one or more of (C) an acid generator, (D) a surfactant, (E) a crosslinking agent, and (F) a plasticizer.

[0029] A protective film-forming composition containing such a component can be made to have superior coating properties or filling / planarizing properties.

[0030] It is also preferable that the protective film-forming composition provides a protective film that is resistant to an ammonia-containing hydrogen peroxide solution.

[0031] Furthermore, it is preferable that the protective film-forming composition is such that when a silicon substrate on which the protective film has been formed is immersed in 1.0 mass % hydrogen peroxide water containing 0.5 mass % ammonia at 70°C for 5 minutes, peeling of the protective film is not observed.

[0032] Such a protective film-forming composition has sufficient resistance to alkaline hydrogen peroxide solution, thereby increasing the options for processable substrates and silicon intermediate films that can be removed by wet etching.

[0033] The present invention also provides a substrate for use in manufacturing a semiconductor device, which comprises a substrate on which a protective film is formed by curing the above protective film-forming composition.

[0034] A protective film formed by curing the protective film-forming composition of the present invention has both high filling and planarizing properties, and is therefore free of microvoids due to insufficient filling or unevenness on the surface of the protective film due to insufficient planarization. Substrates for semiconductor device manufacturing that are planarized with such a protective film have a wide process margin during patterning, making it possible to manufacture semiconductor devices with a high yield.

[0035] The present invention also provides a method for forming a protective film that is used in the manufacturing process of a semiconductor device, which comprises spin-coating the above-mentioned protective film-forming composition onto a substrate to be processed, and then heat-treating the substrate to which the protective film-forming composition has been applied in an inert gas atmosphere at a temperature of 50°C or higher and 600°C or lower for a period of 10 to 7200 seconds to obtain a cured film.

[0036] The present invention also provides a method for forming a protective film that is used in the manufacturing process of a semiconductor device, which comprises spin-coating the above-mentioned protective film-forming composition onto a substrate to be processed, heat-treating the substrate to which the protective film-forming composition has been applied in air at a temperature of 50°C or higher and 250°C or lower for 5 to 600 seconds to form a coating film, and subsequently heat-treating the substrate in an inert gas atmosphere at a temperature of 200°C or higher and 600°C or lower for 10 to 7200 seconds to obtain a cured film.

[0037] The protective film formed by the method of the present invention and applied in the manufacturing process of a semiconductor device has high heat resistance and advanced filling / planarization properties, and when used in the manufacturing process of a semiconductor device, it improves the yield of the semiconductor device.

[0038] At this time, it is preferable that the oxygen concentration in the inert gas is 1% or less.

[0039] The protective film-forming composition of the present invention can be sufficiently cured without generating sublimation even when heated in such an inert gas atmosphere, and can form a protective film that has excellent adhesion to the substrate.

[0040] Furthermore, it is preferable that the substrate to be processed has a structure or step having a height of 30 nm or more.

[0041] The method for forming a protective film of the present invention is particularly useful when forming a flat protective film on such a substrate to be processed.

[0042] The present invention also provides a method for forming a pattern on a substrate to be processed, comprising the steps of: (I-1) forming a protective film on a substrate to be processed using the protective film-forming composition; (I-2) forming a silicon-containing resist interlayer film on the protective film using a silicon-containing resist interlayer film material; (I-3) forming a resist upper layer film on the silicon-containing resist intermediate film using a photoresist composition; (I-4) forming a circuit pattern on the resist upper layer film; (I-5) a step of transferring the pattern to the silicon-containing resist intermediate film by etching using the resist upper layer film on which the pattern has been formed as a mask; (I-6) a step of transferring a pattern to the protective film by etching using the silicon-containing resist intermediate film to which the pattern has been transferred as a mask; and (I-7) forming a pattern on the substrate to be processed using the protective film onto which the pattern has been transferred as a mask; The present invention provides a pattern forming method comprising the steps of:

[0043] Furthermore, the present invention provides a method for forming a pattern on a substrate to be processed, comprising the steps of: (II-1) forming a protective film on a substrate to be processed using the protective film-forming composition; (II-2) forming a silicon-containing resist intermediate film on the protective film using a silicon-containing resist intermediate film material; (II-3) forming an organic anti-reflective coating on the silicon-containing resist intermediate film; (II-4) forming a resist upper layer film on the organic antireflective coating using a photoresist composition to form a four-layer film structure, and forming a circuit pattern on the resist upper layer film; (II-5) a step of transferring a pattern to the organic antireflective coating and the silicon-containing resist intermediate film by etching using the resist upper layer film on which the pattern has been formed as a mask; (II-6) a step of transferring a pattern to the protective film by etching using the silicon-containing resist intermediate film to which the pattern has been transferred as a mask; and (II-7) forming a pattern on the substrate to be processed using the protective film onto which the pattern has been transferred as a mask; The present invention provides a pattern forming method comprising the steps of:

[0044] The present invention also provides a method for forming a pattern on a substrate to be processed, comprising the steps of: (III-1) forming a protective film on a substrate to be processed using the protective film-forming composition; (III-2) forming an inorganic hard mask selected from a silicon oxide film, a silicon nitride film, a silicon oxynitride film, a titanium oxide film, and a titanium nitride film on the protective film; (III-3) forming a resist upper layer film on the inorganic hard mask using a photoresist composition; (III-4) forming a circuit pattern on the resist upper layer film; (III-5) a step of transferring the pattern to the inorganic hard mask by etching using the resist upper layer film on which the pattern has been formed as a mask; (III-6) a step of transferring a pattern to the protective film by etching using the inorganic hard mask to which the pattern has been transferred as a mask; and (III-7) forming a pattern on the substrate to be processed using the protective film onto which the pattern has been transferred as a mask; The present invention provides a pattern forming method comprising the steps of:

[0045] The present invention also provides a method for forming a pattern on a substrate to be processed, comprising the steps of: (IV-1) forming a protective film on a substrate to be processed using the protective film-forming composition; (IV-2) forming an inorganic hard mask selected from a silicon oxide film, a silicon nitride film, a silicon oxynitride film, a titanium oxide film, and a titanium nitride film on the protective film; (IV-3) forming an organic anti-reflective coating on the inorganic hard mask; (IV-4) forming a resist upper layer film on the organic antireflective film using a photoresist composition to form a four-layer film structure, and forming a circuit pattern on the resist upper layer film; (IV-5) a step of transferring the pattern to the organic anti-reflective film and the inorganic hard mask by etching using the resist upper layer film on which the pattern has been formed as a mask; (IV-6) a step of transferring a pattern to the protective film by etching using the inorganic hard mask to which the pattern has been transferred as a mask; and (IV-7) forming a pattern on the substrate to be processed using the protective film onto which the pattern has been transferred as a mask; The present invention provides a pattern forming method comprising the steps of:

[0046] The protective film-forming composition of the present invention can be suitably used in various pattern formation methods, such as a three-layer resist process using a silicon-containing resist intermediate film or an inorganic hard mask, or a four-layer resist process using an organic antireflective film in addition to these. In the manufacturing process of a semiconductor device, forming a circuit pattern using such a pattern formation method of the present invention allows semiconductor devices to be manufactured with a high yield. Furthermore, as described above, the protective film formed using the protective film-forming composition of the present invention has good resistance to alkaline hydrogen peroxide solution, and therefore can also be applied to a wet etching process using alkaline hydrogen peroxide solution.

[0047] The inorganic hard mask is preferably formed by a CVD method or an ALD method.

[0048] In the pattern formation method of the present invention, for example, an inorganic hard mask can be formed by such a method.

[0049] Furthermore, the present invention may provide a pattern formation method that further comprises, after step (I-6) or step (II-6), a step of removing the silicon-containing resist intermediate film to which the pattern has been transferred by wet etching using alkaline hydrogen peroxide water.

[0050] The protective film formed using the protective film-forming composition of the present invention has good resistance to alkaline hydrogen peroxide solution, and therefore, the silicon-containing resist intermediate film can be removed by wet etching using alkaline hydrogen peroxide solution as described above.

[0051] Furthermore, the present invention can provide a pattern formation method comprising the step of transferring a pattern to the workpiece substrate by wet etching using alkaline hydrogen peroxide water, using the protective film to which the pattern has been transferred as a mask, in the step (I-7), step (II-7), step (III-7), or step (IV-7).

[0052] The protective film formed using the protective film-forming composition of the present invention has good resistance to alkaline hydrogen peroxide solution, and therefore, as described above, it is possible to transfer a pattern to a substrate to be processed by wet etching using alkaline hydrogen peroxide solution.

[0053] Furthermore, in the present invention, the pattern forming method may include a step of performing ion implantation using the protective film onto which the pattern has been transferred as a mask, thereby patterning the substrate to be processed, in the step (I-7), step (II-7), step (III-7), or step (IV-7).

[0054] Such a pattern forming method is particularly suitable for ion implantation processing of a substrate having an uneven surface.

[0055] In this case, after the step of patterning the substrate to be processed by ion implantation, a step of removing the silicon-containing resist intermediate film to which the pattern has been transferred by wet etching using alkaline hydrogen peroxide water may be further included.

[0056] Since the protective film formed using the protective film-forming composition of the present invention has good resistance to alkaline hydrogen peroxide solution, it is also possible to remove the silicon-containing resist intermediate film after pattern processing by ion implantation by wet etching using alkaline hydrogen peroxide solution as described above.

[0057] In forming the circuit pattern, it is preferable to form the circuit pattern by lithography using light having a wavelength of 10 nm or more and 300 nm or less, direct drawing with an electron beam, nanoimprinting, or a combination thereof.

[0058] In forming the circuit pattern, it is preferable to develop the circuit pattern using an alkali developer or an organic solvent.

[0059] In the pattern forming method of the present invention, such circuit pattern forming means and developing means can be suitably used.

[0060] Furthermore, it is preferable to use, as the substrate to be processed, a semiconductor device substrate or a semiconductor device substrate having any one of a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, and a metal oxide nitride film formed thereon.

[0061] In this case, it is preferable to use a substrate to be processed that contains silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or an alloy thereof.

[0062] According to the pattern forming method of the present invention, a pattern can be formed by processing the above-mentioned substrate to be processed. [Effects of the Invention]

[0063] As described above, the protective film-forming composition of the present invention can form a cured film without generating by-products even when formed in an inert gas that prevents substrate corrosion, and is useful for forming a protective film that combines high-level filling and planarization properties. Furthermore, the protective film-forming composition of the present invention is a material for forming a protective film that not only has filling / planarization properties but also combines various properties such as heat resistance, etching resistance, adhesion, and alkaline hydrogen peroxide resistance. Therefore, it is extremely useful as a protective film material in multilayer resist methods such as a two-layer resist method, a three-layer resist method using a silicon-containing intermediate film, and a four-layer resist method using a silicon-containing intermediate film and an organic antireflective film, or as a planarization material for semiconductor device manufacturing. Furthermore, the protective film formed from the protective film-forming composition of the present invention has excellent heat resistance, so that even when a CVD hard mask is formed on the protective film, there is no film thickness variation due to thermal decomposition, making it suitable for pattern formation. Furthermore, it is extremely useful in pattern formation methods that use wet etching processes. [Brief explanation of the drawings]

[0064] [Figure 1] FIG. 2 is an explanatory diagram of flattening characteristics in the present invention. [Figure 2] FIG. 1 is an explanatory diagram of an example of a pattern forming method using a three-layer resist method according to the present invention. [Figure 3] FIG. 1 is an explanatory diagram of a method for evaluating filling characteristics in an example. [Figure 4] FIG. 1 is an explanatory diagram of a method for evaluating flattening characteristics in an example. DETAILED DESCRIPTION OF THE INVENTION

[0065] In order to prevent corrosion of the substrate, there has been a demand for the development of a protective film-forming composition that can form a protective film that does not produce by-products even under film-forming conditions in an inert gas, for example, at temperatures of 300°C or higher, that not only has excellent pattern filling and planarization properties when formed on a substrate, but also has good resistance to dry etching during substrate processing, and that does not experience fluctuations in the thickness of the protective film due to thermal decomposition even when a CVD hard mask is formed on top of the protective film, and that is highly compatible with wet etching processes (i.e., resistance to alkaline hydrogen peroxide water).

[0066] The present inventors have further conducted extensive research and have discovered a polymer having a polyimide structure represented by the general formula (1A) containing at least one fluorine atom and a hydroxyl group in its main skeleton, and having a group represented by the general formulas (1B) and (1C) having a triple bond as a thermosetting group, represented by R1, introduced as an end group; a polymer having a polyimide structure represented by the general formula (2A) containing at least one fluorine atom and a polyimide structure represented by the general formula (3A) containing at least one hydroxyl group in its main skeleton, and having a polyimide structure represented by the general formulas (1B) and (1C) The inventors have found that by using a mixture of a polymer having a terminal group represented by the general formula (1B) or (1C) introduced therein, or a polymer having a polyimide structure represented by the general formula (2A) in its main skeleton and having a terminal group represented by the general formula (1B) or (1C) introduced therein, and a polymer having a polyimide structure represented by the general formula (3A) in its main skeleton and having a terminal group represented by the general formula (1B) or (1C) introduced therein, in a protective film-forming composition, the composition has thermosetting properties equivalent to those of conventional underlayer film materials not only in air but also in an inert gas, and also has excellent thermal fluidity, resulting in advanced filling / planarization properties.

[0067] The present inventors have also found that the protective film-forming composition exhibits high heat resistance and good adhesion to substrates, with no change in coating thickness due to thermal decomposition, even when forming a CVD hard mask. Furthermore, the present inventors have found that a mixture of the polymers (I), (II), and (III) provides a protective film-forming composition with excellent alkaline hydrogen peroxide resistance, thereby completing the present invention.

[0068] That is, the present invention provides: (A) a polymer having a fluorine atom and a hydroxyl group represented by either of the following (I) and (II), or a mixture of a polymer having a fluorine atom represented by the following (III) and a polymer having a hydroxyl group; (I) a polymer having a repeating unit represented by the following general formula (1A) containing at least one or more fluorine atoms and hydroxyl groups, the end group of which is a group represented by either of the following general formulas (1B) and (1C); (II) a polymer having a repeating unit represented by the following general formula (2A) containing at least one or more fluorine atoms and a repeating unit represented by the following general formula (3A) containing at least one or more hydroxyl groups: (III) a polymer having a repeating unit containing at least one fluorine atom, represented by the following general formula (2A), and a terminal group having a group represented by the following general formula (1B) or (1C), and a polymer having a repeating unit containing at least one hydroxyl group, represented by the following general formula (3A), and a terminal group having a group represented by the following general formula (1B) or (1C), and (B) an organic solvent; and (C) a protective film-forming composition for alkaline hydrogen peroxide solution. [ka] (In the formula, W1 is a tetravalent organic group which may contain one or more types of fluorine atoms or hydroxyl groups, W2 is a divalent organic group which may contain one or more types of fluorine atoms or hydroxyl groups, and at least one of W1 and W2 contains one or more fluorine atoms and at least one of W1 and W2 contains one or more hydroxyl groups.) [ka] (In the formula, W3 is a tetravalent organic group which may contain one or more types of fluorine atoms, W4 is a divalent organic group which may contain one or more types of fluorine atoms, and at least one of W3 and W4 contains one or more fluorine atoms.) [ka] (In the formula, W5 is a tetravalent organic group which may contain one or more types of hydroxyl groups, W6 is a divalent organic group which may contain one or more types of hydroxyl groups, and at least one of W5 and W6 contains one or more hydroxyl groups.) [ka] [ka] (In the formula, R1 is any of the groups represented by the following formula (1D), and two or more types of R1 may be used in combination.) [ka]

[0069] The present invention will be described in detail below, but the present invention is not limited thereto.

[0070] <Component (A)> The component (A) in the present invention is either the following polymer (I) or polymer (II), or a mixture of polymers (III).

[0071] Polymer (I) The polymer for forming a protective film used in the protective film-forming composition of the present invention is a polymer (polymer (I)) having a repeating unit containing at least one fluorine atom and one hydroxyl group, as represented by the following general formula (1A), and having a terminal group represented by either of the following general formulas (1B) and (1C): [ka] (In the formula, W1 is a tetravalent organic group which may contain one or more types of fluorine atoms or hydroxyl groups, W2 is a divalent organic group which may contain one or more types of fluorine atoms or hydroxyl groups, and at least one of W1 and W2 contains one or more fluorine atoms and at least one of W1 and W2 contains one or more hydroxyl groups.) [ka] [ka] (In the formula, R1 is any of the groups represented by the following formula (1D), and two or more types of R1 may be used in combination.) [ka]

[0072] By forming a pre-cyclized polyimide structure as in (1A), (1B), or (1C) above, elimination reactions such as dehydration, which are by-products of thermal cyclization of polyimide compound precursors such as polyamic acid, are eliminated, suppressing film shrinkage and preventing the loss of flatness of the protective film. Furthermore, by forming a stable imide structure in advance, decomposition due to equilibrium reactions of polyimide compound precursors such as polyamic acid is suppressed, resulting in superior storage stability. Furthermore, the polyimide structure not only provides heat resistance but also contributes to improved adhesion to the substrate. This improved adhesion prevents film peeling when an inorganic hard mask is formed directly on the protective film using CVD or ALD methods, enabling the formation of a protective film with excellent process tolerance. Furthermore, the presence of fluorine atoms and hydroxyl groups in the main backbone of the polyimide structure shown in (1A) above contributes to improved resistance to alkaline hydrogen peroxide solutions. This is thought to be because the fluorine atoms provide the protective film with water repellency against alkaline hydrogen peroxide, while the hydroxyl groups improve adhesion between the protective film and the substrate being processed. This prevents peeling during wet etching using alkaline hydrogen peroxide, resulting in good resistance to alkaline hydrogen peroxide.

[0073] R1 in the above formula (1D) functions as a thermal crosslinking group, and is preferably an ethynyl group or an ethynylphenyl group in terms of curability, heat resistance, and ease of raw material availability.

[0074] Examples of W1 in the above general formula include the following structural formulas, which may have a substituent on the aromatic ring. Examples of the substituent include a hydroxyl group, a trifluoromethyl group, an alkyl group having 1 to 10 carbon atoms, an alkynyl group or alkenyl group having 3 to 10 carbon atoms, an alkyloxy group having 1 to 10 carbon atoms, an alkynyloxy group or alkenyloxy group having 3 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, a nitro group, a halogen group, a nitrile group, an alkoxycarbonyl group having 1 to 10 carbon atoms, and an alkanoyloxy group having 1 to 10 carbon atoms.

[0075] [ka]

[0076] [ka]

[0077] [ka]

[0078] [ka]

[0079] [ka]

[0080] [ka]

[0081] Examples of W2 in the above general formula include the following structural formulas, which may have a substituent on the aromatic ring. Examples of the substituent include a hydroxyl group, a trifluoromethyl group, an alkyl group having 1 to 10 carbon atoms, an alkynyl group or alkenyl group having 3 to 10 carbon atoms, an alkyloxy group having 1 to 10 carbon atoms, an alkynyloxy group or alkenyloxy group having 3 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, a thiol group, a nitro group, a halogen group, a nitrile group, a sulfonic acid group, an alkoxycarbonyl group having 1 to 10 carbon atoms, and an alkanoyloxy group having 1 to 10 carbon atoms.

[0082] [ka]

[0083] [ka]

[0084] [ka]

[0085] [ka]

[0086] By combining one or more types of W1 and W2 with the above-mentioned organic groups, thermal fluidity, heat resistance, and adhesion can be improved. W1 and W2 may each be one type, or a combination of two or more types. However, from the perspective of alkaline hydrogen peroxide resistance, the selected W1 and W2 must contain at least one fluorine atom and one hydroxyl group. That is, at least one of W1 and W2 contains one or more fluorine atoms, and at least one of W1 and W2 contains one or more hydroxyl groups.

[0087] Furthermore, the polymer (I) used in the protective film-forming composition of the present invention preferably contains at least one fluorine atom and one hydroxyl group in W2 in the general formula (1A).

[0088] It is preferable that the main chain has such a partial structure from the viewpoint of achieving both adhesiveness and excellent resistance to alkaline hydrogen peroxide solution.

[0089] Furthermore, in the polymer (I) used in the protective film-forming composition of the present invention, W2 in the general formula (1A) is preferably a group represented by the following general formula (1E). [ka]

[0090] The hexafluoroisopropylidene group introduces flexibility into the main chain, suppressing aggregation between imide groups, thereby achieving both high-level filling / planarization properties and heat resistance. Furthermore, since the above general formula (1E) simultaneously contains a hexafluoroisopropylidene group and a hydroxyl group, the hexafluoroisopropylidene group effectively improves the water repellency of the protective film against alkaline hydrogen peroxide solution, and the hydroxyl group effectively improves the adhesion between the protective film and the substrate to be processed, making it particularly preferable from the perspective of alkaline hydrogen peroxide solution resistance.

[0091] Furthermore, in the polymer used in the protective film-forming composition of the present invention, W1 in the general formula (1A) is preferably a group represented by the following general formula (1F). [ka]

[0092] The hexafluoroisopropylidene group introduces flexibility into the main chain, thereby suppressing aggregation between imide groups, thereby achieving both high-level filling / planarization properties and heat resistance. Furthermore, the hexafluoroisopropylidene group can improve water repellency to alkaline hydrogen peroxide solution, making it preferable from the viewpoint of resistance to alkaline hydrogen peroxide solution. Among the above, a structure having a hexafluoroisopropylidene group and an ether bond as a linking group in the main chain is particularly preferable. The ether bond functions as a flexible linking group and can impart thermal fluidity and solvent solubility, thereby achieving both high-level filling / planarization properties and heat resistance.

[0093] Furthermore, the Mw (weight average molecular weight) of the polymer (I) is preferably 1000 to 10000, more preferably 1000 to 8000, and even more preferably 1500 to 5000. In the present invention, the weight average molecular weight can be the weight average molecular weight (Mw) in terms of polystyrene determined by gel permeation chromatography (GPC) using tetrahydrofuran as an eluent.

[0094] Such a molecular weight ensures solubility in organic solvents and suppresses the generation of sublimation during baking. Furthermore, the polymer (protective film-forming polymer) of component (A) has good thermal fluidity, so that when it is incorporated into a protective film-forming composition, it is possible to not only satisfactorily embed the microstructure formed on the substrate, but also to form a protective film that flattens the entire substrate.

[0095] Polymer (II) The polymer (A) having a fluorine atom and a hydroxyl group may also be a polymer (polymer (II)) having a repeating unit containing at least one fluorine atom, represented by the following general formula (2A), and a repeating unit containing at least one hydroxyl group, represented by the following general formula (3A), in which the terminal group is a group represented by either of the following general formulas (1B) and (1C): [ka] (In the formula, W3 is a tetravalent organic group which may contain one or more types of fluorine atoms, W4 is a divalent organic group which may contain one or more types of fluorine atoms, and at least one of W3 and W4 contains one or more fluorine atoms.) [ka] (In the formula, W5 is a tetravalent organic group which may contain one or more types of hydroxyl groups, W6 is a divalent organic group which may contain one or more types of hydroxyl groups, and at least one of W5 and W6 contains one or more hydroxyl groups.) [ka] [ka] (In the formula, R1 is any of the groups represented by the following formula (1D), and two or more types of R1 may be used in combination.) [ka]

[0096] The polymer (A) used in the present invention contributes to improved resistance to alkaline hydrogen peroxide solution by having fluorine atoms and hydroxyl groups in the main skeleton of the polyimide structure. Therefore, the polymer (A) is not limited to polymer (I) having both fluorine atoms and hydroxyl groups in one repeating unit, but may also be a copolymer (polymer (II)) of a repeating unit having only fluorine atoms and a repeating unit having only hydroxyl groups. Like polymer (I), polymer (II) also provides good filling / planarization properties, heat resistance, adhesion, and resistance to alkaline hydrogen peroxide solution.

[0097] In the repeating unit containing at least one fluorine atom represented by the general formula (2A), W3 is not particularly limited as long as it is a tetravalent organic group that may contain one or more types of fluorine atoms, but for example, it can be a group that does not contain a hydroxyl group among the specific examples of W1 mentioned above. W4 is not particularly limited as long as it is a divalent organic group that may contain one or more types of fluorine atoms, but for example, it can be a group that does not contain a hydroxyl group among the specific examples of W2 mentioned above. However, at least one of W3 and W4 contains one or more fluorine atoms.

[0098] In the repeating unit containing at least one hydroxyl group represented by the general formula (3A), W5 is not particularly limited as long as it is a tetravalent organic group that may contain one or more types of hydroxyl groups, but for example, it can be a group that does not contain a fluorine atom among the specific examples of W1 mentioned above. W6 is not particularly limited as long as it is a divalent organic group that may contain one or more types of hydroxyl groups, but for example, it can be a group that does not contain a fluorine atom among the specific examples of W2 mentioned above. However, at least one of W5 and W6 contains one or more hydroxyl groups.

[0099] The structure of the terminal group and the weight average molecular weight of the polymer (II) are as explained for the polymer (I).

[0100] Polymer mixture (III) Furthermore, the component (A) of the present invention can be a copolymer (polymer (II)) of a repeating unit represented by the general formula (2A) above and a repeating unit represented by the general formula (3A) above, or a mixture (polymer mixture (III)) of a polymer having a repeating unit represented by the general formula (2A) above (polymer (III-1)) and a polymer having a repeating unit represented by the general formula (3A) above (polymer (III-2)).

[0101] Polymer (III-1) is a polymer having a repeating unit containing at least one fluorine atom, represented by the general formula (2A), and a terminal group represented by either of the general formulas (1B) and (1C). In polymer (III-1), the repeating unit represented by the general formula (2A), the structure of the terminal group represented by either of the general formulas (1B) and (1C), and the weight-average molecular weight are as described for polymer (II).

[0102] Polymer (III-2) is a polymer having a repeating unit containing at least one hydroxyl group represented by the general formula (3A) and a terminal group represented by either of the general formulas (1B) and (1C). In polymer (III-2), the repeating unit represented by the general formula (3A), the structure of the terminal group represented by either of the general formulas (1B) and (1C), and the weight-average molecular weight are as described for polymer (II).

[0103] In the present invention, component (A) does not necessarily have to contain both the fluorine atoms and the hydroxyl groups in the main skeleton of the polyimide structure in the same polymer; even if the fluorine atoms in the main skeleton of the polyimide structure and the hydroxyl groups in the main skeleton of the polyimide structure are contained in different polymers, the alkaline hydrogen peroxide resistance can be similarly improved. Therefore, like polymers (I) and (II), polymer mixture (III) also provides good filling / planarization properties, heat resistance, adhesion, and alkaline hydrogen peroxide resistance.

[0104] [(A) Method for producing polymer] The method for producing the polymer of component (A) will be explained using polymer (I) as an example, but polymer (II), polymer (III-1), and polymer (III-2) can also be produced by the same method.

[0105] The polymer used in the protective film-forming composition of the present invention can be obtained by adding an excess of either the diamine or tetracarboxylic anhydride shown below to obtain a polyamic acid intermediate (STEP 1) having an amino group or a carboxylic anhydride active end at the terminal. A polyimide precursor (STEP 2) is then synthesized using a phthalic anhydride derivative or aniline derivative having R1 as a substituent as an end-capping agent, followed by thermal or chemical imidization (STEP 3) to synthesize the polymer (A). The diamine compound or tetracarboxylic anhydride used in synthesizing the polyamic acid compound in STEP 1 and the phthalic anhydride derivative or aniline derivative used for end-capping in STEP 2 can be used alone or in combination. These can be selected and combined appropriately depending on the desired properties. W1, W2, and R1 in the following formula are the same as those defined above.

[0106] (Excess diamine conditions) [ka] [ka] [ka]

[0107] (Tetracarboxylic acid excess condition) [ka] [ka] [ka]

[0108] The synthesis of the polyamic acid intermediate shown in STEP 1 can usually be carried out in an organic solvent at room temperature or, if necessary, under cooling or heating. Examples of the solvent that can be used include alcohols such as methanol, ethanol, isopropyl alcohol, butanol, ethylene glycol, propylene glycol, diethylene glycol, glycerol, ethylene glycol monomethyl ether, propylene glycol monomethyl ether, and propylene glycol monoethyl ether; ethers such as diethyl ether, dibutyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, and 1,4-dioxane; chlorinated solvents such as methylene chloride, chloroform, dichloroethane, and trichloroethylene; and hexachloroethylene. Examples of solvents include hydrocarbons such as benzene, heptane, benzene, toluene, xylene, and cumene; nitriles such as acetonitrile; ketones such as acetone, ethyl methyl ketone, isobutyl methyl ketone, and cyclohexanone; esters such as methyl acetate, ethyl acetate, n-butyl acetate, propylene glycol methyl ether acetate, and γ-butyrolactone; and aprotic polar solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide, N,N-dimethylformamide, and hexamethylphosphoric triamide. These can be used alone or in combination of two or more.

[0109] In these syntheses, a base catalyst can be used as needed. Examples of the base catalyst include inorganic base compounds such as sodium hydrogencarbonate, sodium carbonate, potassium carbonate, calcium carbonate, cesium carbonate, sodium hydroxide, potassium hydroxide, sodium hydride, and potassium phosphate; and organic bases such as triethylamine, diisopropylethylamine, N,N-dimethylaniline, pyridine, and 4-dimethylaminopyridine. These may be used alone or in combination of two or more.

[0110] Reaction methods include adding the diamine compound and tetracarboxylic anhydride all at once to a solvent, adding the diamine compound and tetracarboxylic anhydride individually or in a mixture, followed by dropwise addition of a dispersion or solution, or dissolving or dispersing one of the diamine compound and tetracarboxylic anhydride in a solvent and then adding the other dispersed or dissolved in the solvent. When multiple diamine compounds and tetracarboxylic anhydrides are used, they can be mixed and reacted in advance, or reacted separately and sequentially. When a catalyst is used, the diamine compound and tetracarboxylic anhydride can be added together in one batch, or the catalyst can be dispersed or dissolved in advance and then added dropwise. The ratio of the diamine compound and tetracarboxylic anhydride can be adjusted to achieve the desired Mw range. For example, when using an aniline derivative as the end-capping agent in the next step, the tetracarboxylic anhydride can be used in excess relative to the diamine compound. When using phthalic anhydride as the end-capping agent, the diamine compound can be used in excess relative to the tetracarboxylic anhydride to synthesize a polyamide intermediate. The resulting reaction solution of the polyamic acid intermediate can be used to proceed to the end-capping reaction in STEP 2, but it can also be diluted with an organic solvent to remove unreacted raw materials, catalysts, and other components present in the reaction intermediate system, and then recovered as a powder by separation washing or by crystallization with a poor solvent.

[0111] In the end-capping step of STEP 2, the polyamic acid intermediate reaction solution (or, if recovered as a powder, the solution first) is reacted with an end-capping agent. The same reaction solvent and reaction catalyst can be used as for the polyamic acid intermediate in STEP 1. The reaction method can be the same as in STEP 1, except that the substrate is a polyamic acid intermediate and an aniline derivative or phthalic anhydride is used as the end-capping agent instead of a diamine compound and tetracarboxylic acid anhydride. The resulting polyimide precursor reaction solution can be used directly for the imidization reaction in STEP 3, but it can also be diluted with an organic solvent to remove unreacted raw materials and catalysts present in the reaction intermediate system, followed by separation washing or crystallization with a poor solvent, and recovered as a powder.

[0112] The imidization step shown in STEP 3 can be carried out by thermal or chemical imidization, and these methods can be appropriately selected depending on the thermal stability of the crosslinking group of the target imide compound and the reactivity of the introduced substituent with the reagent used in chemical imidization.

[0113] When thermal imidization is performed, a solvent capable of forming an azeotrope with water is added to the reaction solution of the polyamic acid obtained in STEP 2 (if recovered as a powder, it is dissolved in a soluble solvent beforehand), and the mixture is heated to 100°C to 250°C, and imidization is performed by a dehydration ring-closing reaction while removing the water that is produced.

[0114] Examples of solvents that can form an azeotropic mixture with water include esters such as γ-butyrolactone, polar solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide, and N,N-dimethylformamide, and non-polar solvents such as benzene, toluene, xylene, and mesitylene. These solvents can be used alone or in combination and heated to dehydrate the resulting water by distilling it out of the system.

[0115] When chemical imidization is performed, a base catalyst and an acid anhydride or the like as a dehydrating agent are added to the reaction solution of the polyimide precursor obtained in STEP 2 (if recovered as a powder, it is dissolved in a soluble solvent beforehand), and the mixture is heated to perform imidization.

[0116] Examples of base catalysts used in chemical imidization include pyridine, triethylamine, trimethylamine, tributylamine, and trioctylamine. Of these, pyridine is preferred because it has adequate basicity to promote the reaction. Examples of dehydrating agents include acetic anhydride, trimellitic anhydride, pyromellitic anhydride, trifluoroacetic anhydride, polyphosphoric acid, phosphorus pentoxide, phosphorus pentachloride, and thionyl chloride. Acetic anhydride is preferred from the viewpoint of post-reaction purification. The base catalyst and dehydrating agent may be used alone or in combination. The imidization rate can be controlled by adjusting the amount of catalyst, amount of dehydrating agent, reaction temperature, and reaction time to suit the performance requirements of the target compound.

[0117] The solvent used in this step is not particularly limited as long as it is inert to the reaction. Examples of the solvent include ethers such as diethylene glycol diethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, 1,4-dioxane, etc.; chlorinated solvents such as methylene chloride, chloroform, dichloroethane, trichloroethylene, etc.; hydrocarbons such as hexane, heptane, benzene, toluene, xylene, cumene, etc.; nitriles such as acetonitrile, etc.; ketones such as acetone, ethyl methyl ketone, isobutyl methyl ketone, cyclohexanone, etc.; esters such as methyl acetate, ethyl acetate, n-butyl acetate, propylene glycol methyl ether acetate, γ-butyrolactone, etc.; and aprotic polar solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide, N,N-dimethylformamide, hexamethylphosphoric triamide, etc., and these can be used alone or in combination.

[0118] After the reaction is complete, the protective film-forming composition may be used as is, but it may also be diluted with an organic solvent to remove unreacted raw materials, catalysts, etc. present in the system, and then recovered by separation and washing.

[0119] The organic solvent used for separation washing is not particularly limited as long as it can dissolve the compound and separate into two layers when mixed with water. Examples include hydrocarbons such as hexane, heptane, benzene, toluene, and xylene; esters such as ethyl acetate, n-butyl acetate, and propylene glycol methyl ether acetate; ketones such as methyl ethyl ketone, methyl amyl ketone, cyclohexanone, and methyl isobutyl ketone; ethers such as diethyl ether, diisopropyl ether, methyl tert-butyl ether, and ethyl cyclopentyl methyl ether; chlorinated solvents such as methylene chloride, chloroform, dichloroethane, and trichloroethylene; and mixtures thereof. The washing water used in this process is typically what is known as deionized water or ultrapure water. The number of washes may be one or more times, but washing 10 or more times does not necessarily provide the desired effect, so washing is preferably performed 1 to 5 times.

[0120] In order to remove unreacted raw materials or acidic components from the system during separation and washing, washing may be performed with a basic aqueous solution. Specific examples of the base include alkali metal hydroxides, alkali metal carbonates, alkaline earth metal hydroxides, alkaline earth metal carbonates, ammonia, and organic ammonium.

[0121] Furthermore, in order to remove unreacted raw materials, metal impurities, or basic components from the system during separation and washing, washing with an acidic aqueous solution may be performed. Specific examples of the acid include inorganic acids such as hydrochloric acid, hydrobromic acid, sulfuric acid, nitric acid, phosphoric acid, and heteropolyacids, and organic acids such as oxalic acid, fumaric acid, maleic acid, trifluoroacetic acid, methanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid.

[0122] The separation washing with the basic aqueous solution and the acidic aqueous solution may be carried out either alone or in combination. From the viewpoint of removing metal impurities, the separation washing is preferably carried out in the order of the basic aqueous solution and the acidic aqueous solution.

[0123] After the separation washing with the basic aqueous solution or acidic aqueous solution, washing with neutral water may be carried out subsequently. The number of washings may be one or more times, but is preferably about 1 to 5 times. As the neutral water, the above-mentioned deionized water or ultrapure water may be used. The number of washings may be one or more times, but if the number of washings is too few, the basic components and acidic components may not be removed. Washing 10 or more times does not necessarily provide the effect of washing alone, so it is preferably about 1 to 5 times.

[0124] Furthermore, the reaction product after the separation operation can be recovered as a powder by concentrating the solvent to dryness or crystallizing it under reduced pressure or normal pressure, but it can also be left in a solution state with a moderate concentration to improve operability when preparing the protective film-forming composition. The concentration in this case is preferably 0.1 to 50% by mass, more preferably 0.5 to 30% by mass. At such a concentration, the viscosity is unlikely to increase, preventing a loss of operability, and the amount of solvent is not excessive, making it economical.

[0125] The solvent used in this case is not particularly limited as long as it can dissolve the reaction product (polymer of component (A)). Specific examples include ketones such as cyclohexanone and methyl 2-amyl ketone; alcohols such as 3-methoxybutanol, 3-methyl-3-methoxybutanol, 1-methoxy-2-propanol, and 1-ethoxy-2-propanol; ethers such as propylene glycol monomethyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol monoethyl ether, propylene glycol dimethyl ether, and diethylene glycol dimethyl ether; and esters such as propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, ethyl lactate, ethyl pyruvate, butyl acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, tert-butyl acetate, tert-butyl propionate, and propylene glycol mono tert-butyl ether acetate. These can be used alone or in combination of two or more.

[0126] The synthesis of the above polyimides can be achieved by combining diamine compounds constituting the polymer main chain, tetracarboxylic anhydride derivatives, and phthalic acid derivatives and aniline derivatives used for end-capping, depending on the required performance. Specifically, substituents that contribute to improved solvent solubility, adhesion, and filling / planarization properties, substituents that contribute to etching resistance and film-forming properties, and substituents that contribute to alkaline hydrogen peroxide resistance can be introduced according to the desired performance requirements. Protective film-forming compositions using these polymers can achieve high levels of filling / planarization properties, heat resistance, and alkaline hydrogen peroxide resistance.

[0127] As described above, the polymer of component (A) provides a protective film-forming composition that has heat resistance of 400° C. or higher, high-level filling / planarizing properties, and alkaline hydrogen peroxide resistance.

[0128] In the present invention, planarization properties refer to the ability to planarize the surface of a substrate. With the protective film-forming composition of the present invention, for example, as shown in FIG. 1, by applying a protective film-forming composition 3' onto a substrate 1 and heating it to form a protective film 3, it is possible to reduce a 100 nm step on the substrate 1 to 30 nm or less. The step shape shown in FIG. 1 is a typical example of a step shape on a substrate for manufacturing a semiconductor device, and the step shape of a substrate that can be planarized by the protective film-forming composition of the present invention is, of course, not limited to this.

[0129] <Protective film forming composition> The present invention provides a protective film-forming composition for alkaline hydrogen peroxide solution, which contains (A) the above-mentioned polymer or polymer mixture and (B) an organic solvent. Note that in the protective film-forming composition of the present invention, the above-mentioned component (A) can be used alone or in combination of two or more.

[0130] The organic solvent usable in the protective film-forming composition of the present invention is not particularly limited as long as it dissolves the components contained in the base polymer, the acid generator, crosslinking agent, and other additives described below. Specifically, solvents with a boiling point of less than 180°C, such as those described in paragraphs (0091) and (0092) of JP-A No. 2007-199653, can be used. Among these, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, 2-heptanone, cyclopentanone, cyclohexanone, and mixtures of two or more of these are preferred. The amount of organic solvent blended is preferably 200 to 10,000 parts by weight, more preferably 300 to 5,000 parts by weight, per 100 parts by weight of component (A).

[0131] Such a protective film-forming composition can be applied by spin coating, and because it contains the above-mentioned component (A), it becomes a protective film-forming composition that has heat resistance of 400°C or higher, advanced filling / planarizing properties, and alkaline hydrogen peroxide water resistance.

[0132] Furthermore, in the protective film-forming composition of the present invention, a high-boiling point solvent having a boiling point of 180°C or higher can be added as the organic solvent to the above-mentioned solvent having a boiling point of less than 180°C (a mixture of a solvent having a boiling point of less than 180°C and a solvent having a boiling point of 180°C or higher). The high-boiling point organic solvent is not particularly limited as long as it can dissolve component (A), and may be any of hydrocarbons, alcohols, ketones, esters, ethers, chlorinated solvents, etc., but specific examples include 1-octanol, 2-ethylhexanol, 1-nonanol, 1-decanol, 1-undecanol, ethylene glycol, 1,2-propylene glycol, 1,3-butylene glycol, 2,4-pentanediol, 2-methyl-2,4-pentanediol, 2,5-hexanediol, 2,4-heptanediol, 2-ethyl-1,3-Hexanediol, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, glycerin, n-nonyl acetate, ethylene glycol monohexyl ether, ethylene glycol mono-2-ethylhexyl ether, ethylene glycol monophenyl ether, ethylene glycol monobenzyl ether, diethylene glycol monoethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol monoisobutyl ether, diethylene glycol monohexyl ether, diethylene glycol monophenyl ether, diethylene glycol monobenzyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl methyl ether, triethylene glycol dimethyl ether, triethylene glycol monomethyl ether, triethylene glycol-n-butyl ether, triethylene glycol butyl methyl ether, triethylene Glycol diacetate, tetraethylene glycol dimethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol mono-n-propyl ether, dipropylene glycol mono-n-butyl ether, tripropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, tripropylene glycol mono-n-propyl ether, tripropylene glycol mono-n-butyl ether, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, triacetin, propylene glycol diacetate, dipropylene glycol monomethyl ether acetate, dipropylene glycol methyl-n-propyl ether, dipropylene glycol methyl ether acetate, 1,4-butanediol diacetate, 1,3-butylene glycol diacetate, 1,Examples of the diester include 6-hexanediol diacetate, triethylene glycol diacetate, γ-butyrolactone, dihexyl malonate, diethyl succinate, dipropyl succinate, dibutyl succinate, dihexyl succinate, dimethyl adipate, diethyl adipate, and dibutyl adipate, and these may be used alone or in combination.

[0133] The boiling point of the high-boiling solvent may be appropriately selected according to the temperature at which the protective film-forming composition is heat-treated, and the boiling point of the high-boiling solvent to be added is preferably 180°C to 300°C, and more preferably 200°C to 300°C. Such a boiling point prevents the solvent from volatilizing too quickly during baking (heat treatment) due to a boiling point that is too low, thereby ensuring sufficient thermal fluidity. Furthermore, such a boiling point is so high that the solvent does not remain in the film after baking without volatilizing, and therefore does not adversely affect film properties such as etching resistance.

[0134] Furthermore, when the high-boiling solvent is used, the blending amount of the high-boiling solvent is preferably 1 to 30 parts by mass per 100 parts by mass of the solvent having a boiling point of less than 180° C. If the blending amount is within this range, there is no risk that the blending amount is too small to impart sufficient thermal fluidity during baking, or that the blending amount is too large to remain in the film and lead to deterioration of film properties such as etching resistance.

[0135] In such a protective film-forming composition, the addition of a high-boiling point solvent to the component (A) provides thermal fluidity, resulting in a protective film-forming composition that also has higher filling and planarizing properties.

[0136] <Component (A')> Polymer (IV) In addition to the component (A), the composition for forming a protective film of the present invention may further contain, as component (A'), a polymer (IV) having a repeating unit represented by the following general formula (4A) and having a terminal group represented by the following general formula (2C): [ka] (In the formula, W7 is a tetravalent organic group, and W8 is a divalent organic group.) [ka] (In the formula, R2 represents a monovalent organic group having 1 to 10 carbon atoms, n1 represents an integer of 0 or 1, and n2 and n3 satisfy the relationship 1≦n2≦6 and 0≦n3≦6, and also satisfy the relationship 1≦n2+n3≦6.)

[0137] The amount of polymer (IV) is preferably 1 to 30 parts by mass, and more preferably 1 to 10 parts by mass, per 100 parts by mass of component (A). At such an amount, the terminal hydroxyl groups improve adhesion to the substrate and improve resistance to alkaline hydrogen peroxide solution without deteriorating heat resistance.

[0138] The substituent represented by OR2 can be selected appropriately depending on the intended use, such as an alkyloxy group to impart fluidity, or an alkenyl or alkynyloxy group to impart curability under inert gas. The presence of a substituent represented by OR2 allows the composition to exhibit appropriate solvent solubility and, after curing, to exhibit excellent solvent resistance and heat resistance.

[0139] Furthermore, the Mw (weight average molecular weight) of the polymer (IV) is preferably 1000 to 10000, more preferably 1000 to 8000, and even more preferably 1500 to 5000. In the present invention, the weight average molecular weight can be the weight average molecular weight (Mw) in terms of polystyrene determined by gel permeation chromatography (GPC) using tetrahydrofuran as an eluent.

[0140] In the above general formula (4A), specific examples of W7 include those mentioned above as specific examples of W1.

[0141] In the above general formula (4A), specific examples of W8 include those mentioned above as specific examples of W2.

[0142] Examples of the terminal group represented by the above general formula (2C) include the following structural formulas.

[0143] [ka]

[0144] The polymer (IV) can also be produced by the same method as the above-mentioned method for producing the polymer (A).

[0145] In the protective film-forming composition of the present invention, an acid generator (C) can be added to further accelerate the curing reaction. Acid generators include those that generate acid by thermal decomposition and those that generate acid by light irradiation, and either can be added. Specifically, materials described in paragraphs (0061) to (0085) of JP-A-2007-199653 can be added, but are not limited to these.

[0146] The acid generators can be used alone or in combination of two or more. When an acid generator is added, the amount added is preferably 0.05 to 50 parts, more preferably 0.1 to 10 parts, per 100 parts of component (A).

[0147] A surfactant (D) can be added to the protective film-forming composition of the present invention to improve the coating properties during spin coating. Examples of surfactants that can be used include those described in (0142) to (0147) of JP-A No. 2009-269953. When a surfactant is added, the amount added is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, per 100 parts by mass of component (A).

[0148] Furthermore, a crosslinking agent (E) can be added to the protective film-forming composition of the present invention to enhance curability and further suppress intermixing with the upper layer film. The crosslinking agent is not particularly limited, and a wide variety of known crosslinking agents can be used. Examples include melamine-based crosslinking agents, glycoluril-based crosslinking agents, benzoguanamine-based crosslinking agents, urea-based crosslinking agents, β-hydroxyalkylamide-based crosslinking agents, isocyanurate-based crosslinking agents, aziridine-based crosslinking agents, oxazoline-based crosslinking agents, and epoxy-based crosslinking agents.

[0149] Specific examples of melamine-based crosslinking agents include hexamethoxymethylated melamine, hexabutoxymethylated melamine, alkoxy- and / or hydroxy-substituted derivatives thereof, and partial self-condensates thereof. Specific examples of glycoluril-based crosslinking agents include tetramethoxymethylated glycoluril, tetrabutoxymethylated glycoluril, alkoxy- and / or hydroxy-substituted derivatives thereof, and partial self-condensates thereof. Specific examples of benzoguanamine-based crosslinking agents include tetramethoxymethylated benzoguanamine, tetrabutoxymethylated benzoguanamine, alkoxy- and / or hydroxy-substituted derivatives thereof, and partial self-condensates thereof. Specific examples of urea-based crosslinking agents include dimethoxymethylated dimethoxyethyleneurea, alkoxy- and / or hydroxy-substituted derivatives thereof, and partial self-condensates thereof. Specific examples of β-hydroxyalkylamide-based crosslinking agents include N,N,N',N'-tetra(2-hydroxyethyl)adipamide. Specific examples of isocyanurate crosslinking agents include triglycidyl isocyanurate and triallyl isocyanurate.Specific examples of aziridine crosslinking agents include 4,4'-bis(ethyleneiminocarbonylamino)diphenylmethane and 2,2-bishydroxymethylbutanol-tris[3-(1-aziridinyl)propionate]. Specific examples of the oxazoline-based crosslinking agent include 2,2'-isopropylidenebis(4-benzyl-2-oxazoline), 2,2'-isopropylidenebis(4-phenyl-2-oxazoline), 2,2'-methylenebis4,5-diphenyl-2-oxazoline, 2,2'-methylenebis-4-phenyl-2-oxazoline, 2,2'-methylenebis-4-tertbutyl-2-oxazoline, 2,2'-bis(2-oxazoline), 1,3-phenylenebis(2-oxazoline), 1,4-phenylenebis(2-oxazoline), and 2-isopropenyloxazoline copolymer.Specific examples of epoxy crosslinking agents include diglycidyl ether, ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, poly(glycidyl methacrylate), trimethylolethane triglycidyl ether, trimethylolpropane triglycidyl ether, and pentaerythritol tetraglycidyl ether. When a crosslinking agent is added, the amount added is preferably 1 to 100 parts by mass, and more preferably 5 to 50 parts by mass, per 100 parts by mass of component (A).

[0150] Furthermore, a plasticizer (F) can be added to the protective film-forming composition of the present invention to further improve the planarization / filling properties. The plasticizer is not particularly limited, and a wide variety of known plasticizers can be used. Examples include low-molecular-weight compounds such as phthalates, adipates, phosphates, trimellitates, and citrates, as well as polymers such as polyethers, polyesters, and the polyacetal polymers described in JP-A-2013-253227. When a plasticizer is added, the amount added is preferably 1 to 100 parts by mass, more preferably 5 to 50 parts by mass, per 100 parts by mass of component (A).

[0151] Furthermore, in the protective film-forming composition of the present invention, additives for imparting filling / planarizing properties similar to those of plasticizers are preferably used, such as liquid additives having a polyethylene glycol or polypropylene glycol structure, or thermally decomposable polymers that exhibit a weight loss rate of 40% by mass or more between 30°C and 250°C and have a weight-average molecular weight of 300 to 200,000. These thermally decomposable polymers preferably contain repeating units having an acetal structure represented by the following general formulas (DP1) and (DP1a). When the liquid additive or thermally decomposable polymer is added, the amount added is preferably 1 to 100 parts by mass, more preferably 5 to 50 parts by mass, per 100 parts by mass of component (A).

[0152] [ka] (In the formula, R6 is a hydrogen atom or an optionally substituted saturated or unsaturated monovalent organic group having 1 to 30 carbon atoms. Y1 is a saturated or unsaturated divalent organic group having 2 to 30 carbon atoms.)

[0153] [ka] (In the formula, R 6a is an alkyl group having 1 to 4 carbon atoms. a is a saturated or unsaturated divalent hydrocarbon group having 4 to 10 carbon atoms, which may have an ether bond; and n represents the average number of repeating units and is 3 to 500.

[0154] The protective film-forming composition of the present invention preferably provides a protective film that is resistant to an ammonia-containing aqueous hydrogen peroxide solution. Such a protective film-forming composition can form a protective film that has good resistance to an alkaline aqueous hydrogen peroxide solution, and therefore can be applied to a wet etching process using an alkaline aqueous hydrogen peroxide solution.

[0155] Alkaline hydrogen peroxide solution is commonly used for cleaning semiconductor wafers. In particular, a mixture of 5 parts by weight of deionized water, 1 part by weight of 29% ammonia water, and 1 part by weight of 30% hydrogen peroxide solution is called SC1 (Standard Clean-1) and is a standard chemical solution for cleaning and removing organic impurities and fine particles from wafer surfaces. In addition, alkaline hydrogen peroxide solution can be used to strip or etch some metals and metal compounds, as well as silicon-containing resist intermediate films designed for wet stripping. The composition of the alkaline hydrogen peroxide solution used in these processes is not particularly limited, but it is typically a mixture of deionized water, hydrogen peroxide, and ammonia. In this case, the hydrogen peroxide concentration is preferably 0.1 to 10% by weight, more preferably 0.2 to 5% by weight, and the ammonia concentration is preferably 0.1 to 10% by weight, more preferably 0.2 to 5% by weight. The treatment temperature is preferably 0 to 90°C, more preferably 20 to 80°C.

[0156] Here, we will explain the alkaline hydrogen peroxide resistance test for protective films. First, a protective film-forming composition is formed into a film of approximately 100 nm thickness on a silicon wafer cut into 3 cm squares according to the film formation conditions described below. This wafer piece is immersed in 1.0 mass % hydrogen peroxide solution containing 0.5 mass % ammonia at 70°C for 5 minutes, and then rinsed with deionized water. The protective film can then be visually inspected for peeling from the wafer. If part or all of the protective film peels off, exposing the silicon wafer surface, the protective film used in the test is deemed to have insufficient alkaline hydrogen peroxide resistance.

[0157] That is, it is preferable that the protective film formed from the protective film-forming composition of the present invention is one in which peeling of the protective film is not observed when a silicon substrate on which the protective film has been formed is immersed in 1.0 mass % hydrogen peroxide water containing 0.5 mass % ammonia at 70°C for 5 minutes.

[0158] As described above, the protective film-forming composition of the present invention exhibits heat resistance of 400°C or higher, high filling / planarization properties, and alkaline hydrogen peroxide resistance. Therefore, the protective film-forming composition of the present invention is extremely useful as a protective film-forming composition for multilayer resist methods, such as a two-layer resist method, a three-layer resist method using a silicon-containing resist interlayer or a silicon-containing inorganic hard mask, and a four-layer resist method using a silicon-containing resist interlayer or a silicon-containing inorganic hard mask and an organic antireflective coating. Furthermore, the protective film-forming composition of the present invention does not produce by-products even when formed in an inert gas, and has excellent filling / planarization properties, making it suitable for use as a planarization material in semiconductor device manufacturing processes other than the multilayer resist method. Furthermore, it is also extremely useful in pattern formation methods that employ wet etching processes.

[0159] <Substrates for manufacturing semiconductor devices> The present invention also provides a substrate for use in manufacturing a semiconductor device, which comprises a substrate on which a protective film is formed by curing the above protective film-forming composition.

[0160] A protective film formed by curing the protective film-forming composition of the present invention has both high filling and planarizing properties, resulting in a protective film that is free of microvoids due to insufficient filling or unevenness on the surface due to insufficient planarity. Substrates for semiconductor device manufacturing that are planarized with such a protective film have a wider process margin during patterning, enabling semiconductor devices to be manufactured with a high yield. Furthermore, the protective film has resistance to alkaline hydrogen peroxide solution, making it highly adaptable to wet etching processes.

[0161] <Protective film formation method> The thermal film formation process for forming the protective film can be a single-stage bake, a two-stage bake, or a multi-stage bake (three or more stages), but a single-stage or two-stage bake is economically preferred. Film formation by a single-stage bake is performed, for example, at a temperature of 100°C to 600°C for 5 to 3600 seconds, but preferably at a temperature of 150°C to 500°C for 10 to 7200 seconds. Heat treatment under these conditions can promote planarization and crosslinking due to thermal flow. In the multilayer resist method, a coating-type silicon intermediate film or a CVD hard mask may be formed on the resulting film. When a coating-type silicon intermediate film is used, it is preferable to form the film at a temperature higher than the temperature at which the silicon intermediate film is formed. Typically, the silicon intermediate film is formed at a temperature of 100°C to 400°C, preferably 150°C to 350°C. If the protective film is formed at a temperature higher than this temperature, dissolution of the protective film by the composition for forming a silicon intermediate film can be prevented, and a protective film that does not mix with the composition can be formed.

[0162] When a CVD hard mask is used, it is preferable to form the protective film at a temperature higher than the temperature at which the CVD hard mask is formed, for example, a temperature of 150°C or higher and 500°C or lower.

[0163] On the other hand, in the case of film formation by two-stage baking, the upper limit of the treatment temperature in air is, for example, 300°C or less, preferably 250°C or less, for 10 to 600 seconds, considering the influence of oxygen in the air on the substrate corrosion in the first stage. The second stage bake temperature is higher than the first stage bake temperature, preferably 600°C or less, preferably 500°C or less, for 10 to 7200 seconds. In the multilayer resist method, a coating-type silicon interlayer or CVD hard mask may be formed on the obtained film. When a coating-type silicon interlayer is used, it is preferable to form the film at a temperature higher than the temperature at which the silicon interlayer is formed. Typically, the silicon interlayer is formed at a temperature between 100°C and 400°C, preferably between 150°C and 350°C. Forming the protective film at a temperature higher than this temperature prevents dissolution of the protective film by the silicon interlayer-forming composition and allows for the formation of a protective film that does not mix with the composition.

[0164] When a CVD hard mask is applied in two-stage baking, it is preferable to form the protective film at a temperature higher than the temperature at which the CVD hard mask is formed, such as 150°C or higher and 500°C or lower.

[0165] The present invention also provides a method for forming a protective film used in the manufacturing process of a semiconductor device, which forms a hardened film by heat-treating a substrate to be processed in an atmosphere with an oxygen concentration of 1% or less to prevent corrosion of the substrate to be processed.

[0166] In this protective film forming method, for example, the protective film-forming composition of the present invention is first spin-coated onto a substrate to be processed. After spin-coating, a two-stage bake is performed by first baking in air at 300°C or less, followed by a second stage bake in an atmosphere with an oxygen concentration of 1% or less. In the case of a one-stage bake, the first stage bake in air can be skipped. Examples of the atmosphere during baking include inert gases such as nitrogen, argon, and helium. The protective film-forming composition of the present invention can form a sufficiently cured protective film without generating sublimates, even when fired in such an inert gas atmosphere.

[0167] Furthermore, the protective film forming method of the present invention can be used with a substrate to be processed that has structures or steps with a height of 30 nm or more. As described above, the protective film-forming composition of the present invention has excellent filling / planarizing properties, and therefore can form a flat cured film even if the substrate to be processed has structures or steps (unevenness) with a height of 30 nm or more. In other words, the protective film forming method of the present invention is particularly useful when forming a flat protective film on such a substrate to be processed.

[0168] The thickness of the protective film to be formed may be appropriately selected, but is preferably 30 to 20,000 nm, and more preferably 50 to 15,000 nm.

[0169] The above-described method for forming a protective film can be applied to both the formation of a protective film for pattern formation using the protective film-forming composition of the present invention and the formation of a protective film for a planarization film.

[0170] The present invention provides a method for forming a protective film that is used in the manufacturing process of a semiconductor device, which comprises spin-coating the above-mentioned protective film-forming composition onto a substrate to be processed, and then heat-treating the substrate to which the protective film-forming composition has been applied in an inert gas atmosphere at a temperature of 50°C or higher and 600°C or lower for a period of 10 to 7200 seconds to obtain a cured film.

[0171] The present invention further provides a method for forming a protective film that is used in the manufacturing process of a semiconductor device, which comprises spin-coating the above-mentioned protective film-forming composition onto a substrate to be processed, heat-treating the substrate to which the protective film-forming composition has been applied in air at a temperature of 50°C or higher and 250°C or lower for 5 to 600 seconds, preferably 10 to 600 seconds, to form a coating film, and subsequently heat-treating the substrate in an inert gas atmosphere at a temperature of 200°C or higher and 600°C or lower, preferably 250°C or higher, for 10 to 7200 seconds to obtain a cured film.

[0172] The protective film formed by the method of the present invention and applied in the manufacturing process of a semiconductor device has high heat resistance and advanced filling / planarization properties, and when used in the manufacturing process of a semiconductor device, it improves the yield of the semiconductor device.

[0173] In this protective film forming method, first, the protective film-forming composition of the present invention is spin-coated onto a substrate to be processed. By using the spin-coating method, good embedding properties can be obtained. After spin-coating, the composition is baked (heat-treated) to promote planarization by thermal flow and crosslinking reaction. This baking process can evaporate the solvent in the protective film-forming composition, thereby preventing mixing even when a resist top layer or a silicon-containing resist intermediate layer is formed on the protective film.

[0174] <Pattern formation method> [Three-layer resist method using silicon-containing resist interlayer] The present invention also provides a method for forming a pattern on a substrate to be processed, comprising the steps of: (I-1) forming a protective film on a substrate to be processed using the protective film-forming composition; (I-2) forming a silicon-containing resist interlayer film on the protective film using a silicon-containing resist interlayer film material; (I-3) forming a resist upper layer film on the silicon-containing resist intermediate film using a photoresist composition; (I-4) forming a circuit pattern on the resist upper layer film; (I-5) a step of transferring the pattern to the silicon-containing resist intermediate film by etching using the resist upper layer film on which the pattern has been formed as a mask; (I-6) a step of transferring a pattern to the protective film by etching using the silicon-containing resist intermediate film to which the pattern has been transferred as a mask; and (I-7) forming a pattern on the substrate to be processed using the protective film onto which the pattern has been transferred as a mask; The present invention provides a pattern forming method comprising the steps of:

[0175] The substrate to be processed is preferably a semiconductor device substrate, or a semiconductor device substrate having any of a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal carbide oxide film, and a metal oxynitride film formed thereon. More specifically, although not particularly limited, substrates such as Si, α-Si, p-Si, SiO, SiN, SiON, W, TiN, and Al, or a substrate having the above-mentioned metal film formed thereon as a layer to be processed, may be used.

[0176] The work layer may be a low-k film or a stopper film thereof, such as Si, SiO2, SiON, SiN, p-Si, α-Si, W, W-Si, Al, Cu, or Al-Si, and may be formed to a thickness of typically 50 to 10,000 nm, particularly 100 to 5,000 nm. When forming the work layer, the substrate and the work layer are made of different materials.

[0177] The metal constituting the substrate to be processed is preferably silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or an alloy thereof.

[0178] Furthermore, it is preferable to use a substrate to be processed that has a structure or step with a height of 30 nm or more.

[0179] When a protective film is formed on a substrate to be processed using the protective film-forming composition of the present invention, the above-described protective film-forming method of the present invention may be applied.

[0180] Next, a resist interlayer (silicon-containing resist interlayer) is formed on the protective film using a resist interlayer material containing silicon atoms. Polysiloxane-based interlayer materials are preferred as silicon-containing resist interlayer materials. By imparting anti-reflection properties to the silicon-containing resist interlayer, reflection can be reduced. For 193 nm exposure, in particular, using a protective film-forming composition containing a large amount of aromatic groups and exhibiting high etching selectivity with respect to the substrate increases the k value and increases substrate reflection. However, by providing the silicon-containing resist interlayer with absorption that results in an appropriate k value, reflection can be reduced, reducing substrate reflection to 0.5% or less. For silicon-containing resist interlayers with anti-reflection properties, anthracene is preferred for 248 nm and 157 nm exposure, while for 193 nm exposure, polysiloxanes that have phenyl groups or light-absorbing groups with silicon-silicon bonds in their pendant structures or polysiloxane structures and that are crosslinked by acid or heat are preferred.

[0181] Next, a resist top layer film is formed on the silicon-containing resist intermediate film using a resist top layer film material composed of a photoresist composition. The resist top layer film material may be either positive or negative, and the same materials as commonly used photoresist compositions can be used. After spin-coating the resist top layer film material, it is preferable to prebake at 60 to 180°C for 10 to 300 seconds. Thereafter, exposure is performed according to a conventional method, followed by post-exposure baking (PEB) and development to obtain a resist top layer film pattern. The thickness of the resist top layer film is not particularly limited, but is preferably 30 to 500 nm, and particularly preferably 50 to 400 nm.

[0182] Next, a circuit pattern (resist upper layer film pattern) is formed on the resist upper layer film, preferably by lithography using light with a wavelength of 10 nm or more and 300 nm or less, direct writing with an electron beam, nanoimprinting, or a combination thereof.

[0183] Examples of exposure light include high-energy rays with a wavelength of 300 nm or less, specifically far ultraviolet rays, KrF excimer laser light (248 nm), ArF excimer laser light (193 nm), F2 laser light (157 nm), Kr2 laser light (146 nm), Ar2 laser light (126 nm), soft X-rays (EUV) of 3 to 20 nm, electron beams (EB), ion beams, X-rays, and the like.

[0184] In forming the circuit pattern, it is preferable to develop the circuit pattern using an alkali developer or an organic solvent.

[0185] Next, the resist top layer film on which the circuit pattern has been formed is used as a mask to etch the silicon-containing resist intermediate film, and the pattern is transferred to the silicon-containing resist intermediate film. The etching of the silicon-containing resist intermediate film using the resist top layer film pattern as a mask is preferably carried out using a fluorocarbon gas. This forms a silicon-containing resist intermediate film pattern.

[0186] Next, the pattern is transferred to the protective film by etching using the silicon-containing resist intermediate film with the transferred pattern as a mask. Since the silicon-containing resist intermediate film exhibits higher etching resistance to oxygen gas or hydrogen gas than organic materials, the etching of the protective film performed using the silicon-containing resist intermediate film pattern as a mask is preferably performed using an etching gas mainly composed of oxygen gas or hydrogen gas. This allows the protective film pattern to be formed.

[0187] Next, a pattern is formed on the substrate to be processed using the protective film with the transferred pattern as a mask. For example, the pattern is transferred to the substrate by etching using the protective film with the transferred pattern as a mask. The subsequent etching of the substrate (layer to be processed) can be performed by a conventional method. For example, if the substrate to be processed is made of SiO2, SiN, or a silica-based low-dielectric-constant insulating film, etching is performed mainly with fluorocarbon-based gases, and if it is made of p-Si, Al, or W, etching is performed mainly with chlorine- or bromine-based gases. When the substrate is processed using etching with fluorocarbon-based gases, the silicon-containing resist intermediate film pattern is stripped simultaneously with the substrate processing. On the other hand, when the substrate is processed using etching with chlorine- or bromine-based gases, a separate dry etching stripping process using fluorocarbon-based gases is required after the substrate processing in order to strip the silicon-containing resist intermediate film pattern.

[0188] A protective film obtained using the protective film-forming composition of the present invention can have excellent etching resistance when etching the substrate to be processed as described above.

[0189] [Four-layer resist method using silicon-containing resist interlayer and organic anti-reflective coating] Furthermore, the present invention provides a method for forming a pattern on a substrate to be processed, comprising the steps of: (II-1) forming a protective film on a substrate to be processed using the protective film-forming composition; (II-2) forming a silicon-containing resist intermediate film on the protective film using a silicon-containing resist intermediate film material; (II-3) forming an organic anti-reflective coating on the silicon-containing resist intermediate film; (II-4) forming a resist upper layer film on the organic antireflective coating using a photoresist composition to form a four-layer film structure, and forming a circuit pattern on the resist upper layer film; (II-5) a step of transferring a pattern to the organic antireflective coating and the silicon-containing resist intermediate film by etching using the resist upper layer film on which the pattern has been formed as a mask; (II-6) a step of transferring a pattern to the protective film by etching using the silicon-containing resist intermediate film to which the pattern has been transferred as a mask; and (II-7) forming a pattern on the substrate to be processed using the protective film onto which the pattern has been transferred as a mask; The present invention provides a pattern forming method comprising the steps of:

[0190] This method can be carried out in the same manner as the three-layer resist method using the silicon-containing resist intermediate film described above, except that an organic antireflective coating (BARC) is formed between the silicon-containing resist intermediate film and the resist top layer film.

[0191] The organic anti-reflection film can be formed by spin coating using a known organic anti-reflection film material.

[0192] [Trilayer resist method using inorganic hard mask] The present invention also provides a method for forming a pattern on a substrate to be processed, comprising the steps of: (III-1) forming a protective film on a substrate to be processed using the protective film-forming composition; (III-2) forming an inorganic hard mask selected from a silicon oxide film, a silicon nitride film, a silicon oxynitride film, a titanium oxide film, and a titanium nitride film on the protective film; (III-3) forming a resist upper layer film on the inorganic hard mask using a photoresist composition; (III-4) forming a circuit pattern on the resist upper layer film; (III-5) a step of transferring the pattern to the inorganic hard mask by etching using the resist upper layer film on which the pattern has been formed as a mask; (III-6) a step of transferring a pattern to the protective film by etching using the inorganic hard mask to which the pattern has been transferred as a mask; and (III-7) forming a pattern on the substrate to be processed using the protective film onto which the pattern has been transferred as a mask; The present invention provides a pattern forming method comprising the steps of:

[0193] This method can be carried out in the same manner as the three-layer resist method using the silicon-containing resist intermediate film described above, except that an inorganic hard mask is formed on the protective film instead of the silicon-containing resist intermediate film.

[0194] An inorganic hard mask selected from a silicon oxide film, a silicon nitride film, and a silicon oxynitride film (SiON film) can be formed by a CVD method, an ALD method, or the like. Methods for forming a silicon nitride film are described, for example, in JP 2002-334869 A and WO 2004 / 066377 A. The thickness of the inorganic hard mask is preferably 5 to 200 nm, more preferably 10 to 100 nm. A SiON film, which is highly effective as an anti-reflective film, is most preferably used as the inorganic hard mask. Since the substrate temperature during SiON film formation is 300 to 500°C, the underlayer film must be able to withstand temperatures of 300 to 500°C. The protective film formed using the protective film-forming composition of the present invention has high heat resistance and can withstand high temperatures of 300 to 500°C. Therefore, an inorganic hard mask formed by a CVD method or an ALD method can be combined with a protective film formed by a spin coating method.

[0195] [Four-layer resist method using inorganic hard mask and organic anti-reflective coating] The present invention also provides a method for forming a pattern on a substrate to be processed, comprising the steps of: (IV-1) forming a protective film on a substrate to be processed using the protective film-forming composition; (IV-2) forming an inorganic hard mask selected from a silicon oxide film, a silicon nitride film, a silicon oxynitride film, a titanium oxide film, and a titanium nitride film on the protective film; (IV-3) forming an organic anti-reflective coating on the inorganic hard mask; (IV-4) forming a resist upper layer film on the organic antireflective film using a photoresist composition to form a four-layer film structure, and forming a circuit pattern on the resist upper layer film; (IV-5) a step of transferring the pattern to the organic anti-reflective film and the inorganic hard mask by etching using the resist upper layer film on which the pattern has been formed as a mask; (IV-6) a step of transferring a pattern to the protective film by etching using the inorganic hard mask to which the pattern has been transferred as a mask; and (IV-7) forming a pattern on the substrate to be processed using the protective film onto which the pattern has been transferred as a mask; The present invention provides a pattern forming method comprising the steps of:

[0196] This method can be carried out in the same manner as the above-mentioned three-layer resist method using an inorganic hard mask, except that an organic antireflective coating (BARC) is formed between the inorganic hard mask and the resist top layer film.

[0197] In particular, when a SiON film is used as the inorganic hard mask, the two-layer anti-reflection coating of the SiON film and BARC makes it possible to suppress reflection even in immersion lithography with a high NA exceeding 1.0. Another benefit of forming a BARC is that it reduces the footing of the resist top layer pattern directly above the SiON film.

[0198] An example of a pattern formation method using the three-layer resist method of the present invention is shown in Figures 2(A) to 2(F). In the three-layer resist method, as shown in Figure 2(A), a protective film 3 is formed on a processable layer 2 formed on a substrate 1 using the protective film-forming composition of the present invention, followed by the formation of a silicon-containing resist intermediate film 4, and then a resist upper layer film 5 is formed thereon. Next, as shown in Figure 2(B), the exposed portion 6 of the resist upper layer film 5 is exposed and subjected to PEB (post-exposure bake). Next, as shown in Figure 2(C), development is performed to form a resist upper layer film pattern 5a. Next, as shown in Figure 2(D), using the resist upper layer film pattern 5a as a mask, the silicon-containing resist intermediate film 4 is dry-etched using a fluorocarbon-based gas to form a silicon-containing resist intermediate film pattern 4a. Next, as shown in Figure 2(E), after removing the resist upper layer film pattern 5a, the protective film 3 is oxygen-plasma etched using the silicon-containing resist intermediate film pattern 4a as a mask to form a protective film pattern 3a. Furthermore, as shown in FIG. 2(F), after removing the silicon-containing resist intermediate film pattern 4a, the processable layer 2 is etched using the protective film pattern 3a as a mask to form a pattern 2a.

[0199] When forming an inorganic hard mask, the silicon-containing resist intermediate film 4 can be replaced with an inorganic hard mask, and when forming a BARC, the BARC can be formed between the silicon-containing resist intermediate film 4 and the resist upper layer film 5. Etching of the BARC can be performed prior to and consecutively with etching of the silicon-containing resist intermediate film 4, or etching of the silicon-containing resist intermediate film 4 can be performed after etching of the BARC alone, for example by changing the etching apparatus.

[0200] (Special processing) Furthermore, application of the pattern forming method of the present invention makes it possible to establish various special processing processes in addition to the general processing processes described above, and is therefore of great industrial value.

[0201] (First aspect) First, as described above, dry etching is generally required to strip the silicon-containing resist interlayer, but in the pattern formation method of the present invention, because the protective film is resistant to alkaline hydrogen peroxide, wet stripping of only the silicon-containing resist interlayer using alkaline hydrogen peroxide is also an option. That is, in the pattern formation method using the three-layer resist process of the present invention, after the above step (I-6) or step (II-6), a step of removing the silicon-containing resist interlayer to which the pattern has been transferred by wet etching using alkaline hydrogen peroxide may be added.

[0202] (Second aspect) Furthermore, when the substrate to be processed is made of W, TiN, etc., wet etching of the substrate with alkaline hydrogen peroxide solution can also be an option when the pattern formation method of the present invention is applied. That is, in the pattern formation method using the three-layer or four-layer resist process of the present invention, the etching method in the above step (I-7), step (II-7), step (III-7), or step (IV-7) may be a step of transferring a pattern to the substrate to be processed by wet etching with alkaline hydrogen peroxide solution using the protective film to which the pattern has been transferred as a mask.

[0203] In one example of this process, first, a protective film is formed on the substrate to be processed, and then a silicon-containing resist intermediate film is formed thereon as needed, followed by a resist top layer film.The resist top layer film is then patterned by a conventional method, and the pattern is then transferred to the protective film by etching.Finally, the substrate to be processed can be patterned by wet etching using the protective film as a mask.

[0204] (Third aspect) In the pattern formation method using the three-layer or four-layer resist process of the present invention, the above-mentioned step (I-7), step (II-7), step (III-7), or step (IV-7) may be a step of patterning the workpiece substrate by ion implantation using the protective film to which the pattern has been transferred as a mask. In this case, after the step of patterning the workpiece substrate by ion implantation, a further step of removing the silicon-containing resist intermediate film to which the pattern has been transferred by wet etching using alkaline hydrogen peroxide water may be added.

[0205] The pattern forming method of the present invention is also suitable for processing a stepped substrate having structures or steps with a height of 30 nm or more. An example of such a process will be described below.

[0206] First, a protective film is formed on the uneven substrate to fill and planarize it, and then a silicon-containing resist intermediate film is formed as needed, followed by a resist top layer film. Next, the resist top layer film is patterned using standard methods, and the pattern is subsequently transferred to the protective film by etching. Next, the substrate can be patterned by ion implantation using the protective film as a mask. The remaining silicon-containing resist intermediate film can be removed by either dry etching or wet etching as needed. Finally, the protective film can be removed by dry etching.

[0207] As described above, the pattern forming method of the present invention makes it possible to form a fine pattern on a substrate to be processed with high precision by using a multilayer resist method. [Example]

[0208] The present invention will be described in more detail below with reference to Synthesis Examples, Comparative Synthesis Examples, Examples, and Comparative Examples, but is not limited thereto. Regarding the molecular weight and dispersity, the weight average molecular weight (Mw) and number average molecular weight (Mn) in terms of polystyrene were determined by gel permeation chromatography (GPC) using tetrahydrofuran as an eluent, and the dispersity (Mw / Mn) was calculated.

[0209] Synthesis Example: Synthesis of polymer for protective film-forming composition and polymer having hydroxyl group at terminal group The polymers (or polymer mixtures) (A1) to (A9) for the protective film-forming composition and the polymers (A10) to (A12) having hydroxyl groups at the terminal groups were synthesized using the following tetracarboxylic acid anhydrides (B1) to (B5), diamine compounds (C1) to (C8), aniline derivatives serving as end-capping agents, and phthalic anhydride derivatives (D1) to (D10).

[0210] Tetracarboxylic acid anhydrides: [ka]

[0211] Diamine compounds: [ka]

[0212] End-capping agent: [ka]

[0213] [Synthesis Example 1] Synthesis of polymer (A1) 17.77 g of tetracarboxylic anhydride (B1), 10.65 g of diamine compound (C1), and 120 g of NMP (N-methyl-2-pyrrolidone) were added and reacted under a nitrogen atmosphere at an internal temperature of 40°C for 3 hours. 3.15 g of end-capping agent (D1) was added to the resulting polyamic acid intermediate solution, and the reaction was continued for another 3 hours at an internal temperature of 40°C to obtain a polyimide precursor solution. 150 g of o-xylene was added to the resulting reaction solution, and the reaction was continued for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, and 400 g of methyl isobutyl ketone was added. The organic layer was washed twice with 100 g of 3% aqueous nitric acid solution, then six times with 100 g of pure water, and then evaporated to dryness under reduced pressure. 100 g of THF (tetrahydrofuran) was added to the residue to form a homogeneous solution, which was then crystallized with 400 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 300 g of diisopropyl ether, and then recovered. The recovered crystals were dried in a vacuum at 70 ° C to obtain polymer (A1). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.

[0214] [ka] (A1): Mw = 3750, Mw / Mn = 1.66

[0215] [Synthesis Example 2] Synthesis of polymer (A2) 15.61 g of tetracarboxylic anhydride (B2), 2.51 g of diamine compound (C2), and 1.94 g of diamine compound (C3) were added to 90 g of NMP (N-methyl-2-pyrrolidone) and reacted for 3 hours at an internal temperature of 40°C under a nitrogen atmosphere. 5.80 g of end-capping agent (D2) was added to the resulting polyamic acid intermediate solution, and the reaction was continued for another 3 hours at an internal temperature of 40°C to obtain a polyimide precursor solution. 120 g of o-xylene was added to the resulting reaction solution, and the reaction was continued for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, and 300 g of methyl isobutyl ketone was added. The organic layer was washed twice with 75 g of 3% aqueous nitric acid solution, then six times with 75 g of pure water, and then evaporated to dryness under reduced pressure. 75 g of THF (tetrahydrofuran) was added to the residue to form a homogeneous solution, which was then crystallized with 300 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 200 g of diisopropyl ether, and then recovered. The recovered crystals were dried in a vacuum at 70 ° C to obtain polymer (A2). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.

[0216] [ka] (A2): Mw = 2480, Mw / Mn = 1.42

[0217] [Synthesis Example 3] Synthesis of polymer (A3) 19.28 g of tetracarboxylic anhydride (B3), 1.92 g of diamine compound (C4), and 1.30 g of diamine compound (C5) were added to 90 g of NMP (N-methyl-2-pyrrolidone) and reacted for 3 hours under a nitrogen atmosphere at an internal temperature of 40°C. 4.22 g of end-capping agent (D3) was added to the resulting polyamic acid intermediate solution, and the reaction was continued for another 3 hours at an internal temperature of 40°C to obtain a polyimide precursor solution. 120 g of o-xylene was added to the resulting reaction solution, and the reaction was continued for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, and 300 g of methyl isobutyl ketone was added. The organic layer was washed twice with 75 g of 3% aqueous nitric acid solution, then six times with 75 g of pure water, and then evaporated to dryness under reduced pressure. 75 g of THF (tetrahydrofuran) was added to the residue to form a homogeneous solution, which was then crystallized with 300 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 200 g of diisopropyl ether, and then recovered. The recovered crystals were dried in a vacuum at 70 ° C to obtain polymer (A3). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.

[0218] [ka] (A3): Mw = 2180, Mw / Mn = 1.28

[0219] [Synthesis Example 4] Synthesis of polymer mixture (A4) The polymer (A4-1) and the polymer (A4-2) used in the polymer mixture (A4) were synthesized as follows.

[0220] [Synthesis Example 4-1] Synthesis of polymer (A4-1) 60 g of NMP (N-methyl-2-pyrrolidone) was added to 6.36 g of tetracarboxylic anhydride (B4) and 3.84 g of diamine compound (C6), and the reaction was carried out under a nitrogen atmosphere at an internal temperature of 40°C for 3 hours. 2.34 g of end-capping agent (D4) was added to the resulting polyamic acid intermediate solution, and the reaction was continued for another 3 hours at an internal temperature of 40°C to obtain a polyimide precursor solution. 80 g of o-xylene was added to the resulting reaction solution, and the reaction was carried out for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, and 200 g of methyl isobutyl ketone was added. The organic layer was washed twice with 50 g of 3% aqueous nitric acid solution, then six times with 50 g of pure water, and then evaporated to dryness under reduced pressure. 50 g of THF (tetrahydrofuran) was added to the residue to form a homogeneous solution, which was then crystallized with 200 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 150 g of diisopropyl ether, and then recovered. The recovered crystals were dried in a vacuum at 70 °C to obtain polymer (A4-1). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.

[0221] [ka] (A4-1): Mw = 2310, Mw / Mn = 1.45

[0222] [Synthesis Example 4-2] Synthesis of polymer (A4-2) 60 g of NMP (N-methyl-2-pyrrolidone) was added to 6.36 g of tetracarboxylic anhydride (B4) and 2.58 g of diamine compound (C3), and the reaction was carried out under a nitrogen atmosphere at an internal temperature of 40°C for 3 hours. 2.34 g of end-capping agent (D4) was added to the resulting polyamic acid intermediate solution, and the reaction was continued for another 3 hours at an internal temperature of 40°C to obtain a polyimide precursor solution. 80 g of o-xylene was added to the resulting reaction solution, and the reaction was continued for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, and 200 g of methyl isobutyl ketone was added. The organic layer was washed twice with 50 g of 3% aqueous nitric acid solution, then six times with 50 g of pure water, and then evaporated to dryness under reduced pressure. 50 g of THF (tetrahydrofuran) was added to the residue to form a homogeneous solution, which was then crystallized with 200 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 150 g of diisopropyl ether, and then recovered. The recovered crystals were dried in a vacuum at 70 °C to obtain polymer (A4-2). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.

[0223] [ka] (A4-2): Mw = 2190, Mw / Mn = 1.43

[0224] [Synthesis Example 5] Synthesis of polymer (A5) 9.64 g of tetracarboxylic anhydride (B3), 2.20 g of diamine compound (C7), and 45 g of NMP (N-methyl-2-pyrrolidone) were added and reacted under a nitrogen atmosphere at an internal temperature of 40°C for 3 hours. 3.48 g of end-capping agent (D2) was added to the resulting polyamic acid intermediate solution, and the reaction was continued for another 3 hours at an internal temperature of 40°C to obtain a polyimide precursor solution. 60 g of o-xylene was added to the resulting reaction solution, and the reaction was continued for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, and 150 g of methyl isobutyl ketone was added. The organic layer was washed twice with 40 g of 3% aqueous nitric acid solution, then six times with 40 g of pure water, and then evaporated to dryness under reduced pressure. 40 g of THF (tetrahydrofuran) was added to the residue to form a homogeneous solution, which was then crystallized with 150 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 120 g of diisopropyl ether, and then recovered. The recovered crystals were dried in a vacuum at 70 °C to obtain polymer (A5). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.

[0225] [ka] (A5): Mw = 2230, Mw / Mn = 1.22

[0226] [Synthesis Example 6] Synthesis of polymer (A6) 10.88 g of tetracarboxylic anhydride (B1), 12.82 g of diamine compound (C7), and 100 g of NMP (N-methyl-2-pyrrolidone) were added and reacted under a nitrogen atmosphere at an internal temperature of 40°C for 3 hours. To the resulting polyamic acid intermediate solution, 1.95 g of end-capping agent (D5) and 2.61 g of end-capping agent (D6) were added, and the reaction was continued for another 3 hours at an internal temperature of 40°C to obtain a polyimide precursor solution. 130 g of o-xylene was added to the resulting reaction solution, and the reaction was continued for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, and 350 g of methyl isobutyl ketone was added. The organic layer was washed twice with 90 g of 3% aqueous nitric acid solution, then six times with 90 g of pure water, and then evaporated to dryness under reduced pressure. 90 g of THF (tetrahydrofuran) was added to the residue to form a homogeneous solution, which was then crystallized with 350 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 250 g of diisopropyl ether, and then recovered. The recovered crystals were dried in a vacuum at 70 ° C to obtain polymer (A6). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.

[0227] [ka] (A6): Mw = 3950, Mw / Mn = 1.70

[0228] [Synthesis Example 7] Synthesis of polymer (A7) 15.71 g of tetracarboxylic anhydride (B5) and 3.66 g of diamine compound (C7) were added to 75 g of NMP (N-methyl-2-pyrrolidone) and reacted for 3 hours at an internal temperature of 40°C under a nitrogen atmosphere. 3.51 g of end-capping agent (D3) was added to the resulting polyamic acid intermediate solution and reacted for an additional 3 hours at an internal temperature of 40°C to obtain a polyimide precursor solution. 90 g of o-xylene was added to the resulting reaction solution, and the reaction was continued for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, and 250 g of methyl isobutyl ketone was added. The organic layer was washed twice with 60 g of 3% aqueous nitric acid solution, then six times with 60 g of pure water, and then evaporated to dryness under reduced pressure. 60 g of THF (tetrahydrofuran) was added to the residue to form a homogeneous solution, which was then crystallized with 250 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 180 g of diisopropyl ether, and then recovered. The recovered crystals were dried in a vacuum at 70 °C to obtain polymer (A7). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.

[0229] [ka] (A7): Mw = 1950, Mw / Mn = 1.21

[0230] [Synthesis Example 8] Synthesis of polymer (A8) 7.86 g of tetracarboxylic anhydride (B5), 9.07 g of diamine compound (C8), and 2.75 g of diamine compound (C7) were added to 75 g of NMP (N-methyl-2-pyrrolidone) and reacted for 3 hours at an internal temperature of 40°C under a nitrogen atmosphere. 4.30 g of end-capping agent (D7) was added to the resulting polyamic acid intermediate solution, and the reaction was continued for another 3 hours at an internal temperature of 40°C to obtain a polyimide precursor solution. 90 g of o-xylene was added to the resulting reaction solution, and the reaction was continued for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, and 250 g of methyl isobutyl ketone was added. The organic layer was washed twice with 60 g of 3% aqueous nitric acid solution, then six times with 60 g of pure water, and then evaporated to dryness under reduced pressure. 60 g of THF (tetrahydrofuran) was added to the residue to form a homogeneous solution, which was then crystallized with 250 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 180 g of diisopropyl ether, and then recovered. The recovered crystals were dried in a vacuum at 70 °C to obtain polymer (A8). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.

[0231] [ka] (A8): Mw = 2560, Mw / Mn = 1.41

[0232] [Synthesis Example 9] Synthesis of polymer (A9) 7.54 g of tetracarboxylic anhydride (B5), 0.80 g of diamine compound (C2), and 0.88 g of diamine compound (C7) were added to 40 g of NMP (N-methyl-2-pyrrolidone) and reacted for 3 hours under a nitrogen atmosphere at an internal temperature of 40 °C. 1.69 g of end-capping agent (D4) was added to the resulting polyamic acid intermediate solution, and the reaction was continued for another 3 hours at an internal temperature of 40 °C to obtain a polyimide precursor solution. 45 g of o-xylene was added to the resulting reaction solution, and the reaction was continued for 9 hours at an internal temperature of 180 °C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, and 120 g of methyl isobutyl ketone was added. The organic layer was washed twice with 30 g of 3% aqueous nitric acid solution, then six times with 30 g of pure water, and then evaporated to dryness under reduced pressure. 30 g of THF (tetrahydrofuran) was added to the residue to form a homogeneous solution, which was then crystallized with 120 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 90 g of diisopropyl ether, and then recovered. The recovered crystals were dried in a vacuum at 70 ° C to obtain polymer (A9). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.

[0233] [ka] (A9): Mw = 2010, Mw / Mn = 1.29

[0234] [Synthesis Example 10] Synthesis of polymer (A10) 16.07 g of tetracarboxylic anhydride (B3), 3.34 g of diamine compound (C2), and 75 g of NMP (N-methyl-2-pyrrolidone) were added and reacted under a nitrogen atmosphere at an internal temperature of 40°C for 3 hours. 3.27 g of end-capping agent (D8) was added to the resulting polyamic acid intermediate solution, and the reaction was continued for another 3 hours at an internal temperature of 40°C to obtain a polyimide precursor solution. 90 g of o-xylene was added to the resulting reaction solution, and the reaction was continued for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, and 250 g of methyl isobutyl ketone was added. The organic layer was washed twice with 60 g of 3% aqueous nitric acid solution, then six times with 60 g of purified water, and then evaporated to dryness under reduced pressure. 60 g of THF (tetrahydrofuran) was added to the residue to form a homogeneous solution, which was then crystallized with 250 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 180 g of diisopropyl ether, and then recovered. The recovered crystals were dried in a vacuum at 70 °C to obtain polymer (A10). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.

[0235] [ka] (A10): Mw = 1970, Mw / Mn = 1.24

[0236] [Synthesis Example 11] Synthesis of polymer (A11) 16.07 g of tetracarboxylic anhydride (B3) and 3.66 g of diamine compound (C7) were added to 75 g of NMP (N-methyl-2-pyrrolidone) and reacted for 3 hours at an internal temperature of 40°C under a nitrogen atmosphere. 4.17 g of end-capping agent (D9) was added to the resulting polyamic acid intermediate solution, and the reaction was continued for another 3 hours at an internal temperature of 40°C to obtain a polyimide precursor solution. 90 g of o-xylene was added to the resulting reaction solution, and the reaction was continued for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, and 250 g of methyl isobutyl ketone was added. The organic layer was washed twice with 60 g of 3% aqueous nitric acid solution, then six times with 60 g of purified water, and then evaporated to dryness under reduced pressure. 60 g of THF (tetrahydrofuran) was added to the residue to form a homogeneous solution, which was then crystallized with 250 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 180 g of diisopropyl ether, and then recovered. The recovered crystals were dried in a vacuum at 70 ° C to obtain polymer (A11). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.

[0237] [ka] (A11): Mw = 2010, Mw / Mn = 1.23

[0238] [Synthesis Example 12] Synthesis of polymer (A12) 15.71 g of tetracarboxylic anhydride (B5) and 5.18 g of diamine compound (C8) were added to 75 g of NMP (N-methyl-2-pyrrolidone) and reacted for 3 hours at an internal temperature of 40°C under a nitrogen atmosphere. 4.78 g of end-capping agent (D10) was added to the resulting polyamic acid intermediate solution, and the reaction was continued for another 3 hours at an internal temperature of 40°C to obtain a polyimide precursor solution. 90 g of o-xylene was added to the resulting reaction solution, and the reaction was continued for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, and 250 g of methyl isobutyl ketone was added. The organic layer was washed twice with 60 g of 3% aqueous nitric acid solution, then six times with 60 g of purified water, and then evaporated to dryness under reduced pressure. 60 g of THF (tetrahydrofuran) was added to the residue to form a homogeneous solution, which was then crystallized with 250 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 180 g of diisopropyl ether, and then recovered. The recovered crystals were dried in a vacuum at 70 °C to obtain polymer (A12). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.

[0239] [ka] (A12): Mw = 2100, Mw / Mn = 1.25

[0240] The comparative polymers (R1) to (R9) were synthesized using the following compounds (E1) to (E10), the tetracarboxylic acid anhydrides (B1), (B3), and (B5), the diamine compounds (C1), (C7), and (C8), and the end-capping agents (D3), (D6), and (D7). A 60:40 mixture of isomers was used for (E10).

[0241] [ka]

[0242] [Synthesis Example 13] Synthesis of polymer (R1) 7.11 g of tetracarboxylic anhydride (B1) and 14.65 g of diamine compound (C7) were added to 120 g of NMP (N-methyl-2-pyrrolidone) and reacted for 3 hours at an internal temperature of 40 °C under a nitrogen atmosphere. 7.11 g of end-capping agent (E1) was added to the resulting polyamic acid intermediate solution, and the reaction was continued for another 3 hours at an internal temperature of 40 °C to obtain a polyimide precursor solution. 150 g of o-xylene was added to the resulting reaction solution, and the reaction was continued for 9 hours at an internal temperature of 180 °C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, and 400 g of methyl isobutyl ketone was added. The organic layer was washed twice with 100 g of 3% aqueous nitric acid solution, then six times with 100 g of pure water, and then evaporated to dryness under reduced pressure. 100 g of THF (tetrahydrofuran) was added to the residue to form a homogeneous solution, which was then crystallized with 400 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 300 g of diisopropyl ether, and then recovered. The recovered crystals were dried in a vacuum at 70 °C to obtain polymer (R1). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.

[0243] [ka] (R1): Mw = 2250, Mw / Mn = 1.32

[0244] [Synthesis Example 14] Synthesis of polymer (R2) 13.33 g of tetracarboxylic anhydride (B1) and 4.40 g of diamine compound (C7) were added to 90 g of NMP (N-methyl-2-pyrrolidone) and reacted under a nitrogen atmosphere at an internal temperature of 40°C for 3 hours. 3.35 g of end-capping agent (E2) was added to the resulting polyamic acid intermediate solution, and the reaction was continued for another 3 hours at an internal temperature of 40°C to obtain a polyimide precursor solution. 120 g of o-xylene was added to the resulting reaction solution, and the reaction was continued for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, and 300 g of methyl isobutyl ketone was added. The organic layer was washed twice with 75 g of 3% aqueous nitric acid solution, then six times with 75 g of purified water, and then evaporated to dryness under reduced pressure. 75 g of THF (tetrahydrofuran) was added to the residue to form a homogeneous solution, which was then crystallized with 300 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 200 g of diisopropyl ether, and then recovered. The recovered crystals were dried in a vacuum at 70 °C to obtain polymer (R2). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.

[0245] [ka] (R2): Mw = 2140, Mw / Mn = 1.29

[0246] [Synthesis Example 15] Synthesis of polymer (R3) 12.57 g of tetracarboxylic anhydride (B5) and 14.65 g of diamine compound (C7) were added to 120 g of NMP (N-methyl-2-pyrrolidone) and reacted for 3 hours at an internal temperature of 40°C under a nitrogen atmosphere. 3.92 g of end-capping agent (E3) was added to the resulting polyamic acid intermediate solution, and the reaction was continued for another 3 hours at an internal temperature of 40°C to obtain a polyimide precursor solution. 150 g of o-xylene was added to the resulting reaction solution, and the reaction was continued for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, and 400 g of methyl isobutyl ketone was added. The organic layer was washed twice with 100 g of 3% aqueous nitric acid solution, then six times with 100 g of pure water, and then evaporated to dryness under reduced pressure. 100 g of THF (tetrahydrofuran) was added to the residue to form a homogeneous solution, which was then crystallized with 400 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 300 g of diisopropyl ether, and then recovered. The recovered crystals were dried in a vacuum at 70 °C to obtain polymer (R3). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.

[0247] [ka] (R3): Mw = 2360, Mw / Mn = 1.36

[0248] [Synthesis Example 16] Synthesis of polymer (R4) 150 g of N-methylpyrrolidone was added to 30.00 g of tetracarboxylic anhydride (B1). A homogeneous solution was formed under a nitrogen atmosphere at an internal temperature of 40°C. Then, 14.74 g of amine compound (E4) was added and the reaction was continued for 3 hours at an internal temperature of 40°C to obtain an amic acid solution. 200 g of o-xylene was added to the resulting amic acid solution, and the reaction was continued for 9 hours at an internal temperature of 150°C while removing the resulting low-boiling substances and water from the system to perform dehydration imidization. After the reaction was completed, the mixture was cooled to room temperature and crystallized in 1000 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 500 g of diisopropyl ether, and then recovered. The recovered crystals were dried in vacuo at 70°C to obtain imide compound (R4').

[0249] [ka]

[0250] Next, 15.00 g of the resulting imide compound (R4'), 1.36 g of the aldehyde compound (E5), and 60 g of 2-methoxy-1-propanol were mixed under a nitrogen atmosphere at an internal temperature of 80°C to form a homogeneous solution. Then, 1.5 g of a 20% solution of paratoluenesulfonic acid in 2-methoxy-1-propanol was slowly added and stirred at an internal temperature of 110°C for 8 hours. After cooling to room temperature, 200 g of methyl isobutyl ketone was added. The organic layer was washed five times with 50 g of purified water and then evaporated to dryness under reduced pressure. 50 g of THF was added to the residue, and the polymer was reprecipitated with 200 g of hexane. The precipitated polymer was separated by filtration and dried under reduced pressure to obtain polymer (R4). The weight-average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, yielding the following results.

[0251] [ka] (R4): Mw = 2820, Mw / Mn = 1.72

[0252] [Synthesis Example 17] Synthesis of polymer (R5) 15.55 g of tetracarboxylic anhydride (B1) and 14.62 g of diamine compound (E6) were added to 120 g of NMP (N-methyl-2-pyrrolidone), and the reaction was carried out under a nitrogen atmosphere at an internal temperature of 40°C for 3 hours. 5.16 g of end-capping agent (D7) was added to the resulting polyamic acid intermediate solution, and the reaction was continued for another 3 hours at an internal temperature of 40°C to obtain a polyimide precursor solution. 4.00 g of pyridine was added to the resulting reaction solution, and 12.25 g of acetic anhydride was slowly added dropwise. The reaction was then carried out at an internal temperature of 60°C for 4 hours to carry out imidization. After the reaction was completed, the mixture was cooled to room temperature, and 400 g of methyl isobutyl ketone was added. The organic layer was washed twice with 100 g of 3% aqueous nitric acid solution, then six times with 100 g of pure water, and then evaporated to dryness under reduced pressure. 100 g of THF (tetrahydrofuran) was added to the residue to form a homogeneous solution, which was then crystallized from 400 g of methanol. The precipitated crystals were separated by filtration, washed twice with 300 g of methanol, and then recovered. The recovered crystals were dried in a vacuum at 70 °C to obtain polymer (R5). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.

[0253] [ka] (R5): Mw = 4320, Mw / Mn = 1.72

[0254] [Synthesis Example 18] Synthesis of polymer (R6) 13.33 g of tetracarboxylic anhydride (B1) and 7.32 g of diamine compound (E7) were added to 70 g of NMP (N-methyl-2-pyrrolidone), and the reaction was carried out under a nitrogen atmosphere at an internal temperature of 40°C for 3 hours. 2.11 g of end-capping agent (D3) was added to the resulting polyamic acid intermediate solution, and the reaction was continued for another 3 hours at an internal temperature of 40°C to obtain a polyimide precursor solution. 2.37 g of pyridine was added to the resulting reaction solution, and 7.35 g of acetic anhydride was slowly added dropwise. The reaction was then carried out at an internal temperature of 60°C for 4 hours to carry out imidization. After the reaction was completed, the mixture was cooled to room temperature, and 240 g of methyl isobutyl ketone was added. The organic layer was washed twice with 60 g of 3% aqueous nitric acid solution, then six times with 60 g of pure water, and then evaporated to dryness under reduced pressure. 60 g of THF (tetrahydrofuran) was added to the residue to form a homogeneous solution, which was then crystallized from 240 g of methanol. The precipitated crystals were separated by filtration, washed twice with 240 g of methanol, and then recovered. The recovered crystals were dried in a vacuum at 70 °C to obtain polymer (R6). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.

[0255] [ka] (R6): Mw = 3780, Mw / Mn = 1.67

[0256] [Synthesis Example 19] Synthesis of polymer (R7) 7.71 g of tetracarboxylic anhydride (B3) and 15.55 g of diamine compound (C8) were added to 70 g of NMP (N-methyl-2-pyrrolidone) and reacted for 3 hours under a nitrogen atmosphere at an internal temperature of 40°C. 6.20 g of end-capping agent (D7) was added to the resulting polyamic acid intermediate solution, and the reaction was continued for another 3 hours at an internal temperature of 40°C to obtain a polyimide precursor solution. 2.37 g of pyridine was added to the resulting reaction solution, and 7.35 g of acetic anhydride was slowly added dropwise. The reaction was continued for 4 hours at an internal temperature of 60°C to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, and 240 g of methyl isobutyl ketone was added. The organic layer was washed twice with 60 g of 3% aqueous nitric acid solution, then six times with 60 g of purified water. The organic layer was then evaporated to dryness under reduced pressure. 60 g of THF (tetrahydrofuran) was added to the residue to form a homogeneous solution, which was then crystallized from 240 g of methanol. The precipitated crystals were separated by filtration, washed twice with 240 g of methanol, and then recovered. The recovered crystals were dried in a vacuum at 70 °C to obtain polymer (R7). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.

[0257] [ka] (R7): Mw = 2420, Mw / Mn = 1.26

[0258] [Synthesis Example 20] Synthesis of polymer (R8) 18.34 g of tetracarboxylic anhydride (E8) and 8.30 g of diamine compound (C8) were added to 100 g of NMP (N-methyl-2-pyrrolidone), and the reaction was carried out under a nitrogen atmosphere at an internal temperature of 40°C for 3 hours. 5.62 g of end-capping agent (D3) was added to the resulting polyamic acid intermediate solution, and the reaction was continued for another 3 hours at an internal temperature of 40°C to obtain a polyimide precursor solution. 3.16 g of pyridine was added to the resulting reaction solution, and 9.80 g of acetic anhydride was slowly added dropwise. The reaction was then carried out at an internal temperature of 60°C for 4 hours to carry out imidization. After the reaction was completed, the mixture was cooled to room temperature, and 320 g of methyl isobutyl ketone was added. The organic layer was washed twice with 80 g of 3% aqueous nitric acid solution, then six times with 80 g of pure water, and then evaporated to dryness under reduced pressure. 80 g of THF (tetrahydrofuran) was added to the residue to form a homogeneous solution, which was then crystallized from 320 g of methanol. The precipitated crystals were separated by filtration, washed twice with 240 g of methanol, and then recovered. The recovered crystals were dried in a vacuum at 70 °C to obtain polymer (R8). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.

[0259] [ka] (R8): Mw = 2240, Mw / Mn = 1.27

[0260] [Synthesis Example 21] Synthesis of polymer (R9) 50 g of THF was added to 6.32 g of compound (E9), and a homogeneous solution was prepared in an ice bath under a nitrogen atmosphere. 4.00 g of diamine compound (E10) and 3.34 g of triethylamine, which had been dissolved in 20 g of NMP, were slowly added dropwise, followed by a reaction at room temperature for 1 hour. 14.28 g of compound (C1) and 100 g of NMP were then added to the reaction solution, and the reaction was continued for 3 hours at an internal temperature of 40 °C. 11.18 g of end-capping agent (D6) was then added to obtain a polyimide precursor. 150 g of o-xylene was added to the resulting reaction solution, and the reaction was continued for 9 hours at an internal temperature of 180 °C, while removing the resulting low-boiling substances and water from the system. After the reaction was completed, the mixture was cooled to room temperature and crystallized in 600 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 200 g of diisopropyl ether, and then recovered. The recovered crystals were dried in a vacuum at 70 °C to obtain (R9). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.

[0261] [ka] (R9): Mw = 2930, Mw / Mn = 1.42

[0262] Preparation of protective film-forming compositions (UDL-1 to 22, comparative UDL-1 to 9) The polymers (A1) to (A12) and (R1) to (R9) were used, and the high-boiling solvents used were (S1) 1,6-diacetoxyhexane (boiling point 260°C), (S2) γ-butyrolactone (boiling point 204°C), and (S3) tripropylene glycol monomethyl ether (boiling point 242°C). The polymers were dissolved in propylene glycol monomethyl ether acetate (PGMEA) containing 0.1% by mass of FC-4430 (manufactured by Sumitomo 3M Limited) and cyclohexanone (CyHO) in the proportions shown in Table 1, and then filtered through a 0.1 μm fluororesin filter to prepare protective film-forming compositions (UDL-1 to 22, Comparative UDL-1 to 9).

[0263] [Table 1]

[0264] Example 1 Solvent Resistance Measurement (Examples 1-1 to 1-22, Comparative Examples 1-1 to 1-9) The protective film-forming compositions (UDL-1 to 22, comparative UDL-1 to 9) prepared above were applied to silicon substrates and baked at 450°C for 60 seconds under a nitrogen stream with an oxygen concentration controlled to 0.2% or less. The film thickness was then measured, and PGMEA solvent was dispensed onto the substrate, left for 30 seconds, spin-dried, and baked at 100°C for 60 seconds to evaporate the PGMEA. The film thickness was then measured and the difference in film thickness before and after PGMEA treatment was determined. The results are shown in Table 2.

[0265] [Table 2]

[0266] As shown in Table 2, the protective film-forming compositions of the present invention (Examples 1-1 to 1-22) had a film retention rate of 99% or more after PGMEA treatment, indicating that a crosslinking reaction occurred even in a nitrogen atmosphere, demonstrating sufficient solvent resistance. In contrast, in Comparative Examples 1-1, 1-2, and 1-4, which used polyimides without crosslinking groups, the film retention rate after PGMEA treatment was about 70%, indicating insufficient solvent resistance. These results indicate that R1, introduced as a substituent, effectively functions as a thermal crosslinking group.

[0267] Example 2 Evaluation of Heat Resistance Characteristics (Examples 2-1 to 2-22, Comparative Examples 2-1 to 2-9) The above protective film-forming compositions (UDL-1 to 22, Comparative UDL-1 to 9) were each coated onto a silicon substrate and baked in air at 180°C for 60 seconds to form a 200 nm coating film, and film thickness A was measured. This substrate was then baked for an additional 10 minutes at 450°C in a nitrogen stream with an oxygen concentration controlled to 0.2% or less, and film thickness B was measured. The results are shown in Table 3.

[0268] [Table 3]

[0269] As shown in Table 3, the protective film-forming compositions of the present invention (Examples 2-1 to 2-22) showed a film thickness loss of less than 1% even after baking at 450°C. The protective film-forming compositions of the present invention maintained their film thickness before high-temperature baking even after baking at 450°C, demonstrating high heat resistance. In contrast, when compared with Comparative Examples 2-1, 2-2, and 2-4, which used polyimides lacking crosslinking groups, the protective film-forming compositions of the present invention formed dense films due to thermal crosslinking via the terminal crosslinking group R1, demonstrating excellent heat resistance. Furthermore, Comparative Example 2-3, which has a bismaleimide structure as the crosslinking group, exhibited solvent resistance due to thermal crosslinking under the conditions of Example 1, but did not exhibit sufficient heat resistance due to thermal crosslinking via the bismaleimide structure under the conditions of long-term high-temperature treatment as in Example 2.

[0270] Example 3: Evaluation of filling characteristics (Examples 3-1 to 3-22, Comparative Examples 3-1 to 3-9) As shown in Figure 3, each of the protective film-forming compositions (UDL-1 to 22, Comparative UDL-1 to 9) was applied to a SiO2 wafer substrate with a dense hole pattern (hole diameter 0.16 μm, hole depth 0.50 μm, center-to-center distance between adjacent two holes 0.32 μm). The composition was baked on a hot plate at 450°C for 60 seconds in a nitrogen stream with an oxygen concentration controlled to 0.2% or less, forming a protective film 8. The substrate used was a base substrate 7 (SiO2 wafer substrate) with a dense hole pattern as shown in Figure 3(G) (overhead view) and (H) (cross-sectional view). The cross-sectional shape of each wafer substrate was observed using a scanning electron microscope (SEM) to confirm whether the holes were filled with the protective film and free of voids (air gaps). The results are shown in Table 4. When a protective film-forming composition with poor filling properties was used, voids were generated within the holes in this evaluation. When a protective film-forming composition with good filling properties is used, the protective film fills the hole without leaving any voids, as shown in FIG. 3(I) in this evaluation.

[0271] [Table 4]

[0272] As shown in Table 4, it was confirmed that the protective film-forming compositions of the present invention (Examples 3-1 to 3-22) were capable of filling hole patterns without generating voids and had good filling properties. On the other hand, it was confirmed that voids were generated in Comparative Examples 3-1 to 3-4, resulting in poor filling properties. From these results, it can be seen that the protective film-forming compositions of the present invention ensure heat resistance through the thermosetting reaction and have improved filling properties. On the other hand, in Comparative Examples 3-1 to 3-4, even though Comparative UDL-3 exhibits solvent resistance, voids were generated due to insufficient heat resistance, and good filling properties were not obtained.

[0273] Example 4 Evaluation of Planarization Characteristics (Examples 4-1 to 4-22, Comparative Examples 4-1 to 4-9) Each of the protective film-forming compositions (UDL-1 to 22, comparative UDL-1 to 9) was applied to a base substrate 9 (SiO2 wafer substrate) having a large isolated trench pattern (Figure 4(J), trench width 10 μm, trench depth 0.10 μm). The substrate was then baked at 450°C for 60 seconds in a nitrogen stream with an oxygen concentration controlled to 0.2% or less. The step difference (delta10 in Figure 4(K)) between the trench and non-trench portions of the protective film 10 was then observed using a Park Systems NX10 atomic force microscope (AFM). The results are shown in Table 5. In this evaluation, the smaller the step difference, the better the planarization characteristics. Note that in this evaluation, a 0.10 μm deep trench pattern was planarized using a protective film-forming composition with a typical film thickness of approximately 0.2 μm, which provides strict evaluation conditions for evaluating the superiority or inferiority of planarization characteristics.

[0274] [Table 5]

[0275] As shown in Table 5, the protective film-forming compositions of the present invention (Examples 4-1 to 4-22) exhibited smaller step differences between the trench and non-trench portions of the protective film compared to Comparative Examples 4-1 to 4-4, demonstrating superior planarization characteristics. Comparative Example 4-3 exhibited poor heat resistance, as shown in the results of the heat resistance evaluation in Example 2, resulting in significant film thickness loss due to high-temperature baking, accentuating the difference in film thickness between the upper and lower portions of the step and deteriorating planarization, resulting in the results described above. Similarly, Comparative Examples 4-1, 4-2, and 4-4 used non-crosslinked polyimide, resulting in significant film thickness loss due to high-temperature treatment and poor planarization. Furthermore, when Examples 4-11 to 4-13 and 4-20 to 4-22, in which a high-boiling-point solvent was added, were compared with Examples 4-3, 4-5, 4-7, and 4-17 to 4-19, in which no high-boiling-point solvent was added, it was clear that the addition of a high-boiling-point solvent further improved planarization.

[0276] Example 5: Evaluation of alkaline hydrogen peroxide resistance (Examples 5-1 to 5-22, Comparative Examples 5-1 to 5-9) The protective film-forming compositions (UDL-1 to 22, Comparative UDL-1 to 9) were each applied to a silicon wafer substrate with a 300 nm SiO2 film formed thereon and baked at 450°C for 60 seconds under a nitrogen stream with an oxygen concentration controlled to 0.2% or less to form a 200 nm thick protective film (resist underlayer film). The wafers were then cut into 2 cm wide strips. The wafer pieces were immersed in a 1.0 wt% hydrogen peroxide solution containing 0.5 wt% ammonia at 70°C for 5 minutes, rinsed with deionized water, and dried. The protective film was visually inspected for peeling from the wafer. If the protective film peeled in part or entirely, exposing the silicon wafer surface, the tested protective film was deemed to have insufficient alkaline hydrogen peroxide resistance. The evaluation results are shown in Table 6.

[0277] [Table 6]

[0278] As shown in Table 6, no peeling of the protective film was observed in any of the protective film-forming compositions of the present invention (Examples 5-1 to 5-22). On the other hand, peeling of the protective film was observed in Comparative Examples 5-1 to 5-9, even though heat resistance and solvent resistance were ensured. This demonstrates that polyimide compounds containing both fluorine atoms and hydroxyl groups, such as those of the present invention, have excellent alkaline hydrogen peroxide resistance. Furthermore, it was also demonstrated that the addition of polyimides containing hydroxyl groups at the terminal groups also provided excellent alkaline hydrogen peroxide resistance.

[0279] Example 6 Pattern Formation Test (Examples 6-1 to 6-22, Comparative Examples 6-1 to 6-9) The protective film-forming compositions (UDL-1 to 22, Comparative UDL-1 to 9) were each applied to a silicon wafer substrate with a 300 nm SiO2 film and baked at 450 °C for 60 seconds under a nitrogen stream with an oxygen concentration controlled to 0.2% or less to form a 200 nm protective film (resist underlayer). A CVD-SiON hard mask was then formed on top of the SiO2 film. An organic antireflective coating material (ARC-29A, manufactured by Nissan Chemical Industries, Ltd.) was then applied and baked at 210 °C for 60 seconds to form an 80 nm organic antireflective coating. An ArF single-layer resist from the resist overlayer material was then applied and baked at 105 °C for 60 seconds to form a 100 nm photoresist film. An immersion protective film material (TC-1) was applied to the photoresist film and baked at 90 °C for 60 seconds to form a 50 nm protective film.

[0280] The resist top layer material (ArF single-layer resist) was prepared by dissolving a polymer (RP1), an acid generator (PAG1), and a basic compound (Amine1) in a solvent containing 0.1 mass% of FC-430 (manufactured by Sumitomo 3M Limited) in the proportions shown in Table 7, and filtering the solution through a 0.1 μm fluororesin filter.

[0281] [Table 7]

[0282] The polymer (RP1), acid generator (PAG1), and basic compound (Amine1) used in the resist top layer material (ArF single layer resist) are shown below.

[0283] [ka]

[0284] [ka]

[0285] The immersion protective film material (TC-1) was prepared by dissolving the protective film polymer (PP1) in an organic solvent in the ratio shown in Table 8 and filtering the solution through a 0.1 μm fluororesin filter.

[0286] [Table 8]

[0287] The polymer (PP1) used in the immersion protective film material (TC-1) is shown below. [ka]

[0288] The resist was then exposed using an ArF immersion exposure system (Nikon Corporation; NSR-S610C, NA 1.30, σ 0.98 / 0.65, 35-degree dipole s-polarized illumination, 6% halftone phase-shift mask), baked at 100°C for 60 seconds (PEB), and developed in a 2.38% by mass aqueous solution of tetramethylammonium hydroxide (TMAH) for 30 seconds to obtain a 55 nm 1:1 positive line-and-space pattern.

[0289] Next, the organic anti-reflective coating and the CVD-SiON hard mask were dry-etched using a Tokyo Electron etching system, Telius, with the resist pattern as a mask to form a hard mask pattern, and the protective film was then etched using the resulting hard mask pattern as a mask to form a protective film pattern. The etching conditions were as follows:

[0290] Transfer conditions for resist pattern onto SiON hard mask. Chamber pressure 10.0Pa RF power 1,500W CF4 gas flow rate 75sccm O2 gas flow rate 15sccm Time 15sec

[0291] Conditions for transferring the hard mask pattern to the protective film. Chamber pressure 2.0Pa RF power 500W Ar gas flow rate: 75 sccm O2 gas flow rate: 45sccm Time 120sec

[0292] The formation of the protective film pattern was confirmed by top-down SEM observation of the wafer after protective film etching. The wafer was then cut into 2 cm wide pieces, and these wafer pieces were immersed in a 1.0 wt% hydrogen peroxide solution containing 0.5 wt% ammonia at 70°C for 5 minutes, rinsed with deionized water, dried, and then observed using an optical microscope to evaluate the presence or absence of peeling of the protective film pattern. The evaluation results are shown in Table 9.

[0293] [Table 9]

[0294] As shown in Table 9, the results for the protective film-forming compositions of the present invention (Examples 6-1 to 6-22) confirmed that in all cases, the resist upper layer film pattern was successfully transferred to the protective film, confirming that the protective film-forming composition of the present invention is suitable for use in microfabrication using a multilayer resist method. Furthermore, it was also confirmed that the formed protective film pattern had good alkaline hydrogen peroxide solution resistance. In Comparative Example 6-3, a pattern was successfully formed despite insufficient heat resistance. Furthermore, in Comparative Examples 6-1, 6-2, and 6-4, both heat resistance and solvent resistance were insufficient, but patterns were successfully formed. On the other hand, in Comparative Examples 6-1 to 6-9, peeling of the formed protective film pattern was observed even though heat resistance and solvent resistance were ensured. Therefore, the protective film-forming composition and pattern-forming method of the present invention are particularly useful for enabling the manufacture of semiconductor devices by microfabrication that combines chemical etching using alkaline hydrogen peroxide solution or the like with a multilayer resist method.

[0295] Example 7 Pattern Formation Test (Examples 7-1 to 7-22, Comparative Examples 7-1 to 7-9) The above protective film-forming compositions (UDL-1 to 22, Comparative UDL-1 to 9) were each applied to an SiO2 wafer substrate having a trench pattern (trench width 10 μm, trench depth 0.10 μm) and baked at 450°C for 60 seconds in a nitrogen stream with an oxygen concentration controlled to 0.2% or less. A coated film was formed in the same manner as in Example 6, followed by patterning and dry etching to form a protective film pattern. Furthermore, the obtained protective film pattern was used as a mask to etch the SiO2 film. The etching conditions were as follows:

[0296] Transfer conditions for the protective film pattern onto the SiO2 film. Chamber pressure 2.0Pa RF power 2,200W C5F 12 Gas flow rate: 20sccm C2F6 gas flow rate: 10sccm Ar gas flow rate: 300sccm O2 gas flow rate 60sccm Time 90sec

[0297] The cross section of the pattern was observed using an electron microscope (S-4700) manufactured by Hitachi, Ltd. The results are shown in Table 10.

[0298] [Table 10]

[0299] As shown in Table 10, in the results for the protective film-forming compositions of the present invention (Examples 7-1 to 7-22), the resist upper layer film pattern was ultimately transferred successfully to the substrate in all cases, confirming that the protective film-forming compositions of the present invention are suitable for use in microfabrication using a multilayer resist method. On the other hand, in Comparative Examples 7-1 to 7-4, even though heat resistance and solvent resistance were ensured, pattern collapse occurred during pattern processing due to poor pattern filling, and ultimately a good pattern could not be obtained.

[0300] From the above, the protective film-forming composition of the present invention has heat resistance of 400°C or higher even in an oxygen-free inert gas, and also has high-level filling / planarizing properties, making it extremely useful as a protective film-forming composition for use in multilayer resist methods.Furthermore, the pattern formation method of the present invention using this composition can form fine patterns with high precision even when the workpiece is a substrate with steps, making it suitable for use in multilayer resist processes for fine patterning in semiconductor device manufacturing.In particular, it is applicable to multilayer resist processes including wet etching processing, making it extremely useful industrially.

[0301] This specification includes the following inventions.

[0302] [1]: (A) a polymer having a fluorine atom and a hydroxyl group represented by either of the following (I) and (II), or a mixture of a polymer having a fluorine atom represented by the following (III) and a polymer having a hydroxyl group; (I) a polymer having a repeating unit represented by the following general formula (1A) containing at least one fluorine atom and a hydroxyl group, the end group of which is a group represented by either of the following general formulas (1B) and (1C); (II) a polymer having a repeating unit represented by the following general formula (2A) containing at least one fluorine atom and a repeating unit represented by the following general formula (3A) containing at least one hydroxyl group: (III) a polymer having a repeating unit containing at least one fluorine atom, represented by the following general formula (2A), and a terminal group being a group represented by the following general formula (1B) or (1C); (III) a mixture of a polymer having a repeating unit containing at least one hydroxyl group, represented by the following general formula (3A), and a terminal group being a group represented by the following general formula (1B) or (1C); and (B) an organic solvent. [ka] (In the formula, W1 is a tetravalent organic group which may contain one or more types of fluorine atoms or hydroxyl groups, W2 is a divalent organic group which may contain one or more types of fluorine atoms or hydroxyl groups, and at least one of W1 and W2 contains one or more fluorine atoms and at least one of W1 and W2 contains one or more hydroxyl groups.) [ka] (In the formula, W3 is a tetravalent organic group which may contain one or more types of fluorine atoms, W4 is a divalent organic group which may contain one or more types of fluorine atoms, and at least one of W3 and W4 contains one or more fluorine atoms.) [ka] (In the formula, W5 is a tetravalent organic group which may contain one or more types of hydroxyl groups, W6 is a divalent organic group which may contain one or more types of hydroxyl groups, and at least one of W5 and W6 contains one or more hydroxyl groups.) [ka] [ka] (In the formula, R1 is any of the groups represented by the following formula (1D), and two or more types of R1 may be used in combination.) [ka]

[0303] [2]: The protective film-forming composition for alkaline hydrogen peroxide solution according to the above [1], characterized in that W2 in the general formula (1A) contains at least one fluorine atom and one hydroxyl group.

[0304] [3]: A protective film-forming composition for alkaline hydrogen peroxide solution according to [1] or [2] above, characterized in that W2 in the general formula (1A) is a group represented by the following general formula (1E): [ka]

[0305] [4]: A protective film-forming composition for alkaline hydrogen peroxide solution according to [1], [2], or [3] above, characterized in that W1 in the general formula (1A) is any one of groups represented by the following general formula (1F): [ka]

[0306] [5]: The protective film-forming composition for alkaline hydrogen peroxide solution according to [1], [2], [3], or [4], further comprising, as component (A'), a polymer (IV) having a repeating unit represented by the following general formula (4A) and having a terminal group represented by the following general formula (2C): [ka] (In the formula, W7 is a tetravalent organic group, and W8 is a divalent organic group.) [ka] (In the formula, R2 represents a monovalent organic group having 1 to 10 carbon atoms, n1 represents an integer of 0 or 1, and n2 and n3 satisfy the relationship 1≦n2≦6 and 0≦n3≦6, and also satisfy the relationship 1≦n2+n3≦6.)

[0307] [6]: A protective film-forming composition for alkaline hydrogen peroxide solution according to [1], [2], [3], [4], or [5], characterized in that the weight-average molecular weight of component (A) is 1,000 to 10,000.

[0308] [7]: The protective film-forming composition for alkaline hydrogen peroxide solution according to [1], [2], [3], [4], [5], or [6], characterized in that the component (B) is a mixture of one or more organic solvents having a boiling point of less than 180°C and one or more organic solvents having a boiling point of 180°C or higher.

[0309] [8]: A protective film-forming composition for alkaline hydrogen peroxide solution according to [1], [2], [3], [4], [5], [6], or [7], characterized in that the protective film-forming composition further contains one or more of (C) an acid generator, (D) a surfactant, (E) a crosslinking agent, and (F) a plasticizer.

[0310] [9]: A protective film-forming composition for alkaline hydrogen peroxide solution according to [1], [2], [3], [4], [5], [6], [7], or [8], characterized in that the protective film-forming composition provides a protective film that is resistant to ammonia-containing hydrogen peroxide solution.

[0311]

[10] : A protective film-forming composition for alkaline hydrogen peroxide solution according to [9] above, characterized in that when a silicon substrate on which the protective film has been formed is immersed in 1.0 mass % hydrogen peroxide solution containing 0.5 mass % ammonia at 70°C for 5 minutes, no peeling of the protective film is observed.

[0312]

[11] : A substrate for manufacturing a semiconductor device, characterized in that a protective film formed on the substrate is formed by curing the protective film-forming composition described in [1], [2], [3], [4], [5], [6], [7], [8], [9], or

[10] .

[0313]

[12] : A method for forming a protective film used in the manufacturing process of a semiconductor device, comprising spin-coating a protective film-forming composition according to any one of [1], [2], [3], [4], [5], [6], [7], [8], [9], and

[10] above onto a substrate to be processed, and then heat-treating the substrate to which the protective film-forming composition has been applied in an inert gas atmosphere at a temperature of 50°C or higher and 600°C or lower for a period of 10 to 7200 seconds to obtain a cured film.

[0314]

[13] : A method for forming a protective film used in the manufacturing process of a semiconductor device, comprising spin-coating a protective film-forming composition according to any one of [1], [2], [3], [4], [5], [6], [7], [8], [9], and

[10] above onto a substrate to be processed, heat-treating the substrate to which the protective film-forming composition has been applied in air at a temperature of 50°C or higher and 250°C or lower for 5 to 600 seconds to form a coating film, and subsequently heat-treating the substrate in an inert gas atmosphere at a temperature of 200°C or higher and 600°C or lower for 10 to 7200 seconds to obtain a cured film.

[0315]

[14] : The method for forming a protective film according to

[12] or

[13] above, wherein the oxygen concentration in the inert gas is 1% or less.

[0316]

[15] : The method for forming a protective film according to

[12] ,

[13] , or

[14] , characterized in that the substrate to be processed has a structure or step having a height of 30 nm or more.

[0317]

[16] : A method for forming a pattern on a workpiece substrate, comprising: (I-1) forming a protective film on a workpiece substrate using the protective film-forming composition described in [1], [2], [3], [4], [5], [6], [7], [8], [9], or

[10] above; (I-2) forming a silicon-containing resist intermediate film on the protective film using a silicon-containing resist intermediate film material; (I-3) forming a resist upper layer film on the silicon-containing resist intermediate film using a photoresist composition; (I-4) forming a circuit pattern on the resist upper layer film; (I-5) transferring the pattern to the silicon-containing resist intermediate film by etching using the resist upper layer film on which the pattern has been formed as a mask; (I-6) transferring the pattern to the protective film by etching using the silicon-containing resist intermediate film on which the pattern has been transferred as a mask; and (I-7) forming a pattern on the workpiece substrate using the protective film on which the pattern has been transferred as a mask.

[0318]

[17] : A method for forming a pattern on a substrate to be processed, comprising: (II-1) forming a protective film on a substrate to be processed using the protective film-forming composition described in [1], [2], [3], [4], [5], [6], [7], [8], [9], or

[10] ; (II-2) forming a silicon-containing resist intermediate film on the protective film using a silicon-containing resist intermediate film material; (II-3) forming an organic antireflective film on the silicon-containing resist intermediate film; and (II-4) forming a photoresist composition on the organic antireflective film. A pattern forming method comprising the steps of: forming a resist top layer film to form a four-layer film structure; and forming a circuit pattern on the resist top layer film; (II-5) using the resist top layer film on which the pattern has been formed as a mask to transfer the pattern to the organic antireflective film and the silicon-containing resist intermediate film by etching; (II-6) using the silicon-containing resist intermediate film on which the pattern has been transferred as a mask to transfer the pattern to the protective film by etching; and (II-7) using the protective film on which the pattern has been transferred as a mask to form a pattern on the substrate to be processed.

[0319]

[18] : A method for forming a pattern on a substrate to be processed, comprising: (III-1) forming a protective film on a substrate to be processed using the protective film-forming composition according to any one of [1], [2], [3], [4], [5], [6], [7], [8], [9], and

[10] ; (III-2) forming an inorganic hard mask selected from a silicon oxide film, a silicon nitride film, a silicon oxynitride film, a titanium oxide film, and a titanium nitride film on the protective film; and (III-3) forming a photoresist composition on the inorganic hard mask. A pattern forming method comprising the steps of: forming a resist top layer film; (III-4) forming a circuit pattern on the resist top layer film; (III-5) transferring the pattern to the inorganic hard mask by etching using the resist top layer film on which the pattern has been formed as a mask; (III-6) transferring the pattern to the protective film by etching using the inorganic hard mask on which the pattern has been transferred as a mask; and (III-7) forming a pattern on the substrate to be processed using the protective film on which the pattern has been transferred as a mask.

[0320]

[19] : A method for forming a pattern on a substrate to be processed, comprising: (IV-1) forming a protective film on a substrate to be processed using the protective film-forming composition according to any one of [1], [2], [3], [4], [5], [6], [7], [8], [9], and

[10] ; (IV-2) forming an inorganic hard mask selected from a silicon oxide film, a silicon nitride film, a silicon oxynitride film, a titanium oxide film, and a titanium nitride film on the protective film; (IV-3) forming an organic antireflective film on the inorganic hard mask; and (IV-4) forming a photoresist on the organic antireflective film. (IV-5) using the resist top layer film on which the pattern has been formed as a mask to transfer the pattern to the organic antireflective coating and the inorganic hard mask by etching; (IV-6) using the inorganic hard mask on which the pattern has been transferred as a mask to transfer the pattern to the protective film by etching; and (IV-7) using the protective film on which the pattern has been transferred as a mask to form a pattern on the substrate to be processed.

[0321]

[20] : The pattern forming method according to

[18] or

[19] above, wherein the inorganic hard mask is formed by a CVD method or an ALD method.

[0322]

[21] : The pattern forming method according to

[16] or

[17] , further comprising, after step (I-6) or step (II-6), a step of removing the silicon-containing resist intermediate film to which the pattern has been transferred by wet etching using alkaline hydrogen peroxide water.

[0323]

[22] : The pattern forming method according to

[16] ,

[17] ,

[18] ,

[19] , or

[20] , characterized in that in the step (I-7), step (II-7), step (III-7), or step (IV-7), a step of transferring a pattern to the substrate to be processed by wet etching using alkaline hydrogen peroxide water, using the protective film to which the pattern has been transferred, as a mask.

[0324]

[23] : The pattern forming method according to

[16] ,

[17] ,

[18] ,

[19] , or

[20] , characterized in that in the step (I-7), step (II-7), step (III-7), or step (IV-7), a step of patterning the substrate to be processed by ion implantation using the protective film to which the pattern has been transferred as a mask is included.

[0325]

[24] : The pattern forming method according to

[23] above, further comprising a step of removing the silicon-containing resist intermediate film to which the pattern has been transferred by wet etching using alkaline hydrogen peroxide water after the step of patterning the substrate to be processed by the ion implantation.

[0326]

[25] : The pattern forming method according to

[16] ,

[17] ,

[18] ,

[19] ,

[20] ,

[21] ,

[22] ,

[23] , or

[24] , characterized in that in forming the circuit pattern, the circuit pattern is formed by lithography using light having a wavelength of 10 nm or more and 300 nm or less, direct writing with an electron beam, nanoimprinting, or a combination thereof.

[0327]

[26] : The pattern forming method according to

[16] ,

[17] ,

[18] ,

[19] ,

[20] ,

[21] ,

[22] ,

[23] ,

[24] , or

[25] , characterized in that in forming the circuit pattern, the circuit pattern is developed using an alkaline developer or an organic solvent.

[0328]

[27] : The pattern forming method according to

[16] ,

[17] ,

[18] ,

[19] ,

[20] ,

[21] ,

[22] ,

[23] ,

[24] ,

[25] , or

[26] , characterized in that the substrate to be processed is a semiconductor device substrate, or a semiconductor device substrate having any of a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, and a metal oxide nitride film formed thereon.

[0329]

[28] : The pattern forming method according to

[27] above, characterized in that the substrate to be processed contains silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or an alloy thereof.

[0330] The present invention is not limited to the above-described embodiments, which are merely examples, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and that provides similar effects is included within the technical scope of the present invention. [Explanation of symbols]

[0331] 1...substrate, 2...processed layer, 2a...pattern (pattern formed on the processed layer), 3...protective film, 3'...protective film-forming composition, 3a...protective film pattern, 4...silicon-containing resist intermediate film, 4a...silicon-containing resist intermediate film pattern, 5...resist upper layer film, 5a...resist upper layer film pattern, 6...exposed portion, 7... base substrate having a dense hole pattern; 8... protective film; 9...underlying substrate having a giant isolated trench pattern; 10...protective film; delta10: Step difference between the trench portion and the non-trench portion of the protective film 10.

Claims

1. (A) a polymer having a fluorine atom and a hydroxyl group represented by either of the following (I) and (II), or a mixture of a polymer having a fluorine atom and a polymer having a hydroxyl group represented by the following (III): (I) A polymer having a repeating unit containing at least one fluorine atom and one hydroxyl group, represented by the following general formula (1A), and having a terminal group represented by either of the following general formulas (1B) and (1C): (II) A polymer having a repeating unit containing at least one fluorine atom, represented by the following general formula (2A), and a repeating unit containing at least one hydroxyl group, represented by the following general formula (3A), wherein the terminal group is a group represented by either of the following general formulas (1B) and (1C): (III) A mixture of a polymer having a repeating unit containing at least one fluorine atom, represented by the following general formula (2A), and a terminal group represented by any one of the groups represented by the following general formulas (1B) and (1C), and a polymer having a repeating unit containing at least one hydroxyl group, represented by the following general formula (3A), and a terminal group represented by any one of the groups represented by the following general formulas (1B) and (1C), and (B) Organic solvent A protective film-forming composition for alkaline hydrogen peroxide solution, comprising: 【Chemistry 1】 (In the formula, W 1 is a tetravalent organic group which may contain one or more fluorine atoms or hydroxyl groups, W 2 is a divalent organic group which may contain one or more fluorine atoms or hydroxyl groups, and W 1 and W 2 At least one of W 1 and W 2 At least one of the groups contains one or more hydroxyl groups.) 【Chemistry 2】 (In the formula, W 3 is a tetravalent organic group which may contain one or more types of fluorine atoms, W 4 is a divalent organic group which may contain one or more types of fluorine atoms, and W 3 and W 4 At least one of the groups contains one or more fluorine atoms. 【Transformation 3】 (In the formula, W 5 is a tetravalent organic group which may contain one or more hydroxyl groups, W 6 is a divalent organic group which may contain one or more hydroxyl groups, and W 5 and W 6 At least one of the groups contains one or more hydroxyl groups.) 【Chemistry 4】 【Transformation 5】 (In the formula, R 1 is any of the groups represented by the following formula (1D), and two or more R 1 may be used in combination.) 【Transformation 6】

2. W in the general formula (1A) 2 2. The composition for forming a protective film against alkaline hydrogen peroxide solution according to claim 1, wherein the composition contains at least one fluorine atom and one hydroxyl group.

3. W in the general formula (1A) 2 3. The composition for forming a protective film against alkaline hydrogen peroxide solution according to claim 2, wherein is a group represented by the following general formula (1E): 【Transformation 7】

4. W in the general formula (1A) 1 The protective film-forming composition for alkaline hydrogen peroxide solution according to any one of claims 1 to 3, characterized in that: is any one of groups represented by the following general formula (1F): 【Transformation 8】

5. A protective film-forming composition for alkaline hydrogen peroxide solution according to any one of claims 1 to 3, characterized in that it further contains, as component (A'), a polymer (IV) having a repeating unit represented by the following general formula (4A) and having a terminal group represented by the following general formula (2C): 【Chemistry 9】 (In the formula, W 7 is a tetravalent organic group, W 8 is a divalent organic group. 【Chemistry 10】 (In the formula, R 2 represents a monovalent organic group having 1 to 10 carbon atoms, n1 represents an integer of 0 or 1, and n2 and n3 satisfy the relationship 1≦n2≦6 and 0≦n3≦6, and also satisfy the relationship 1≦n2+n3≦6.

6. 4. The protective film-forming composition for alkaline hydrogen peroxide solution according to claim 1, wherein the weight average molecular weight of the component (A) is 1,000 to 10,000.

7. A protective film-forming composition for alkaline hydrogen peroxide solution according to any one of claims 1 to 3, characterized in that the component (B) is a mixture of one or more organic solvents having a boiling point of less than 180°C and one or more organic solvents having a boiling point of 180°C or higher.

8. A protective film-forming composition for alkaline hydrogen peroxide solution according to any one of claims 1 to 3, characterized in that the protective film-forming composition further contains one or more of (C) an acid generator, (D) a surfactant, (E) a crosslinking agent, and (F) a plasticizer.

9. 4. A protective film-forming composition for alkaline hydrogen peroxide solution according to claim 1, characterized in that the protective film-forming composition provides a protective film that is resistant to ammonia-containing hydrogen peroxide solution.

10. The protective film-forming composition for alkaline hydrogen peroxide solution, as described in claim 9, characterized in that when a silicon substrate having the protective film formed thereon is immersed in 1.0 mass % hydrogen peroxide solution containing 0.5 mass % ammonia at 70°C for 5 minutes, no peeling of the protective film is observed.

11. A substrate for manufacturing a semiconductor device, comprising a substrate on which a protective film is formed by curing the protective film-forming composition according to claim 1 .

12. A method for forming a protective film used in the manufacturing process of a semiconductor device, comprising spin-coating the protective film-forming composition according to claim 1 onto a substrate to be processed, and heat-treating the substrate to which the protective film-forming composition has been applied in an inert gas atmosphere at a temperature of 50°C or higher and 600°C or lower for 10 to 7200 seconds to obtain a cured film.

13. A method for forming a protective film used in the manufacturing process of a semiconductor device, comprising spin-coating the protective film-forming composition according to claim 1 onto a substrate to be processed, heat-treating the substrate to which the protective film-forming composition has been applied in air at a temperature of 50°C or higher and 250°C or lower for 5 to 600 seconds to form a coating film, and subsequently heat-treating the substrate to which the protective film-forming composition has been applied in an inert gas atmosphere at a temperature of 200°C or higher and 600°C or lower for 10 to 7200 seconds to obtain a cured film.

14. 14. The method for forming a protective film according to claim 12, wherein the oxygen concentration in the inert gas is set to 1% or less.

15. 14. The method for forming a protective film according to claim 12, wherein the substrate to be processed has a structure or step having a height of 30 nm or more.

16. A method for forming a pattern on a workpiece substrate, comprising: (I-1) forming a protective film on a substrate to be processed using the protective film-forming composition according to claim 1; (I-2) forming a silicon-containing resist intermediate film on the protective film using a silicon-containing resist intermediate film material; (I-3) forming a resist upper layer film on the silicon-containing resist intermediate film using a photoresist composition; (I-4) forming a circuit pattern on the resist upper layer film; (I-5) a step of transferring the pattern to the silicon-containing resist intermediate film by etching using the resist upper layer film on which the pattern has been formed as a mask; (I-6) a step of transferring a pattern to the protective film by etching using the silicon-containing resist intermediate film to which the pattern has been transferred as a mask; and (I-7) forming a pattern on the substrate to be processed using the protective film onto which the pattern has been transferred as a mask; A pattern forming method comprising the steps of:

17. A method for forming a pattern on a workpiece substrate, comprising: (II-1) forming a protective film on a substrate to be processed using the protective film-forming composition according to claim 1; (II-2) forming a silicon-containing resist intermediate film on the protective film using a silicon-containing resist intermediate film material; (II-3) forming an organic anti-reflective coating on the silicon-containing resist intermediate film; (II-4) forming a resist upper layer film on the organic antireflective film using a photoresist composition to form a four-layer film structure, and forming a circuit pattern on the resist upper layer film; (II-5) a step of transferring a pattern to the organic antireflective coating and the silicon-containing resist intermediate film by etching using the resist upper layer film on which the pattern has been formed as a mask; (II-6) A step of transferring a pattern to the protective film by etching using the silicon-containing resist intermediate film to which the pattern has been transferred as a mask; and (II-7) forming a pattern on the substrate to be processed using the protective film to which the pattern has been transferred as a mask; A pattern forming method comprising the steps of:

18. A method for forming a pattern on a workpiece substrate, comprising: (III-1) A step of forming a protective film on a substrate to be processed using the protective film-forming composition according to claim 1; (III-2) forming an inorganic hard mask selected from a silicon oxide film, a silicon nitride film, a silicon oxynitride film, a titanium oxide film, and a titanium nitride film on the protective film; (III-3) forming a resist upper layer film on the inorganic hard mask using a photoresist composition; (III-4) forming a circuit pattern on the resist upper layer film; (III-5) a step of transferring the pattern to the inorganic hard mask by etching using the resist upper layer film on which the pattern has been formed as a mask; (III-6) a step of transferring a pattern to the protective film by etching using the inorganic hard mask to which the pattern has been transferred as a mask; and (III-7) forming a pattern on the substrate to be processed using the protective film onto which the pattern has been transferred as a mask; A pattern forming method comprising the steps of:

19. A method for forming a pattern on a workpiece substrate, comprising: (IV-1) forming a protective film on a substrate to be processed using the protective film-forming composition according to claim 1; (IV-2) forming an inorganic hard mask selected from a silicon oxide film, a silicon nitride film, a silicon oxynitride film, a titanium oxide film, and a titanium nitride film on the protective film; (IV-3) forming an organic anti-reflective coating on the inorganic hard mask; (IV-4) forming a resist upper layer film on the organic antireflective film using a photoresist composition to form a four-layer film structure, and forming a circuit pattern on the resist upper layer film; (IV-5) a step of transferring the pattern to the organic anti-reflective film and the inorganic hard mask by etching using the resist top layer film on which the pattern has been formed as a mask; (IV-6) A step of transferring a pattern to the protective film by etching using the inorganic hard mask to which the pattern has been transferred as a mask; and (IV-7) forming a pattern on the substrate to be processed using the protective film to which the pattern has been transferred as a mask; A pattern forming method comprising the steps of:

20. 20. The pattern formation method according to claim 18, wherein the inorganic hard mask is formed by a CVD method or an ALD method.

21. 18. The pattern forming method according to claim 16, further comprising, after step (I-6) or step (II-6), a step of removing the silicon-containing resist intermediate film to which the pattern has been transferred by wet etching using alkaline hydrogen peroxide water.

22. 20. The pattern formation method according to claim 16, wherein the step (I-7), the step (II-7), the step (III-7), or the step (IV-7) comprises a step of transferring a pattern to the workpiece substrate by wet etching using an alkaline hydrogen peroxide solution, using the protective film to which the pattern has been transferred as a mask.

23. 20. The pattern formation method according to claim 16, wherein the step (I-7), the step (II-7), the step (III-7), or the step (IV-7) comprises a step of patterning the substrate to be processed by performing ion implantation using the protective film to which the pattern has been transferred as a mask.

24. 24. The pattern formation method according to claim 23, further comprising, after the step of patterning the workpiece substrate by ion implantation, a step of removing the silicon-containing resist intermediate film to which the pattern has been transferred by wet etching using alkaline hydrogen peroxide water.

25. 20. The pattern formation method according to claim 16, wherein the circuit pattern is formed by lithography using light having a wavelength of 10 nm or more and 300 nm or less, direct writing with an electron beam, nanoimprinting, or a combination thereof.

26. 20. The pattern forming method according to claim 16, wherein the circuit pattern is developed using an alkali developer or an organic solvent in forming the circuit pattern.

27. 20. The pattern forming method according to claim 16, wherein the workpiece substrate is a semiconductor device substrate, or a semiconductor device substrate having any one of a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, and a metal oxide nitride film formed thereon.

28. 28. The pattern formation method according to claim 27, wherein the substrate to be processed contains silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or an alloy thereof.